Polyethylene Composition

A polyethylene composition with tailored elution profiles addresses the trade-off in conventional films by achieving high density and low hot tack and heat seal initiation temperatures, improving processing and sealing efficiency in packaging applications.

JP7658974B2Active Publication Date: 2025-04-08DOW GLOBAL TECHNOLOGIES LLC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022538166
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-31
Filing Date
2020-12-21
Publication Date
2025-04-08
Estimated Expiration
2040-12-21

AI Technical Summary

Technical Problem

Conventional polyethylene compositions for packaging applications face a trade-off between high density, which improves processing properties, and low hot tack and heat seal initiation temperatures, making them difficult to process and seal effectively.

Method used

A polyethylene composition comprising three distinct polyethylene fractions with specific elution profiles, including a first fraction between 35°C to 70°C, a second fraction between 85°C to 120°C, and a third fraction between 70°C to 85°C, achieving a balance of high density and low hot tack and heat seal initiation temperatures.

Benefits of technology

The composition provides films with improved processing properties and lower hot tack and heat seal initiation temperatures, enhancing the efficiency and effectiveness of packaging applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658974000025
    Figure 0007658974000025
  • Figure 0007658974000026
    Figure 0007658974000026
  • Figure 0007658974000001
    Figure 0007658974000001
Patent Text Reader

Abstract

Embodiments of polyethylene compositions are provided that may include: a first polyethylene fraction comprising at least one peak in a temperature range of 35°C to 70°C in an elution profile via an improved comonomer composition distribution (iCCD) analysis method, the first polyethylene area fraction being the area in the elution profile from 35°C to 70°C, and the first polyethylene fraction area comprising 25% to 65% of the total area of ​​the elution profile; and a second polyethylene fraction comprising at least one peak in a temperature range of 85°C to 120°C in an elution profile, the second polyethylene area fraction being the area in the elution profile from 85°C to 120°C, and the second polyethylene fraction area comprising at least 20% of the total area of ​​the elution profile.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 62 / 955,723, filed December 31, 2019, the entire disclosure of which is incorporated herein by reference.

[0002] The present application relates to polymer compositions, and more specifically to polyethylene compositions and methods for producing the same. [Background technology]

[0003] The use of polyolefin compositions in industries such as packaging applications is generally known. A variety of conventional methods can be used to produce such polyolefin compositions. A variety of polymerization techniques using different catalyst systems have been used to produce such polyolefin compositions suitable for packaging applications. However, in some embodiments, despite the research efforts in developing compositions suitable for packaging applications, there is still a need for improved polyethylene compositions suitable for packaging applications that can have a good balance of physical properties and processability at desired polymer composition density. Summary of the Invention

[0004] The present application discloses polyethylene compositions suitable for packaging applications, films, multi-layer structures, and packaging articles made therefrom. In embodiments, the polyethylene compositions of the present disclosure are suitable for use as heat sealant packaging applications.

[0005] Conventional films, such as those utilizing a sealant layer, typically experience a trade-off between hot tack initiation temperature, heat seal initiation temperature, or both, and the overall density of the film. The density of the composition can affect the processing properties of the film. For example, films including conventional polyethylene compositions with relatively low density tend to provide films that exhibit lower hot tack initiation temperature, heat seal initiation temperature, or both, when compared to films including compositions with relatively high overall density. Polyethylene compositions with relatively low density can also be particularly difficult to process in conventional blown film applications due to the very low melting point and tacky or sticky nature of the material, while films with relatively high overall density often exhibit higher hot tack initiation temperature, heat seal initiation temperature, or both. In packaging applications, lower hot tack and heat seal initiation temperature can be desirable polymer performance properties. Thus, there is a need for films with relatively high density that provide lower hot tack initiation temperature, heat seal initiation temperature, or both. The polyethylene compositions of the present disclosure may provide films having relatively high density and relatively low hot tack initiation temperatures, heat seal initiation temperatures, or both.

[0006] As described in detail herein, the polymer composition may be evaluated by improved comonomers composition distribution (iCCD) analysis. The present disclosure, in some embodiments, may satisfy the above-mentioned needs regarding heat seal initiation temperature, hot tack initiation temperature, and polymer density by providing a polyethylene composition comprising at least three polyethylene fractions, each comprising a desired percentage of the total area of ​​the elution profile in a particular temperature range via iCCD analysis. Such polyethylene compositions may have a desirable hot tack initiation temperature, heat seal initiation temperature, or both, but may not have a desired heat seal initiation temperature, e.g., a heat seal initiation temperature of at least 0.880 g / cm. 3For example, the polyethylene compositions of the present disclosure may have a relatively higher density and a lower hot tack initiation temperature, heat seal initiation temperature, or both, than conventional polymer compositions. Without being bound by theory, it is believed that at least some of the polyethylene compositions described herein may have such properties due, at least in part, to a particular multi-modal elution profile in which the first polyethylene fraction and the second polyethylene fraction exhibit peaks at 35°C-70°C and 85°C-120°C, respectively, in the elution profile from iCCD analysis.

[0007] According to one or more embodiments, a polyethylene composition suitable for packaging applications comprises: (a) a first polyethylene fraction having at least one peak in an elution profile via an improved comonomer composition distribution (iCCD) analytical method within a temperature range of 35° C. to 70° C., the first polyethylene area fraction being an area in the elution profile from 35° C. to 70° C., the first polyethylene fraction area constituting 25% to 65% of the total area of ​​the elution profile; (b) a first polyethylene fraction having at least one peak in an elution profile via an iCCD analytical method within a temperature range of 85° C. to 120° C. and (c) a third polyethylene fraction within a temperature range of 70°C to 85°C in an elution profile via an iCCD analysis method, the third polyethylene area fraction being an area in an elution profile from 70°C to 85°C, and the third polyethylene fraction area comprising less than 10% of the total area of ​​the elution profile. The polyethylene composition may comprise a polyethylene fraction having a molecular weight of 0.880 g / cm or less. 3 ~0.910g / cm 3 The polyethylene composition may have a density of from 0.50 g / 10 min to 6.0 g / 10 min, a melt index (I2) of from 0.50 g / 10 min to 6.0 g / 10 min, and a zero shear viscosity ratio of less than 2.0.

[0008] According to one or more embodiments, the film may comprise the polyethylene composition described above or any of the other embodiments described herein.

[0009] According to one or more embodiments, an article may include the polyethylene composition of any of the above or other embodiments described herein. [Brief description of the drawings]

[0010] The following detailed description of certain embodiments of the present disclosure can be best understood when read in conjunction with the following drawings, in which like structure is indicated with like reference numerals and in which: [Figure 1] 1 is a graph that generally illustrates an iCCD elution profile, according to one or more embodiments described herein. [Diagram 2] FIG. 1 illustrates a schematic of a reactor system useful for producing polyethylene according to one or more embodiments described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Described herein are embodiments of polyethylene compositions. Such polyethylene compositions can be used, for example, in packaging applications. The polyethylene compositions can include a first polyethylene fraction, a second polyethylene fraction, and a third polyethylene fraction. The polyethylene compositions can be included in films (including monolayer films and multilayer films) or other articles such as multilayer structures and packaging materials.

[0012] As used herein, "polyethylene" or "ethylene-based polymer" refers to a polymer containing a majority (>50 mol%) of units derived from ethylene monomer. This includes polyethylene homopolymers or copolymers (meaning that the units are derived from two or more comonomers). Common forms of polyethylene known in the art include low density polyethylene (LDPE), linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), single-site catalyzed linear low density polyethylene (m-LLDPE), including both linear and substantially linear low density resins, ethylene-based plastomers (POP) and ethylene-based elastomers (POE), medium density polyethylene (MDPE), and high density polyethylene (HDPE). These polyethylene materials are generally known in the art, however, the following description may be helpful in understanding the differences between some of these different polyethylene resins.

[0013] As used herein, the term "composition" refers to a mixture of materials that comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.

[0014] The term "LDPE" may also be referred to as "high pressure ethylene polymer", or "highly branched polyethylene" and may be defined to mean that the polymer is partially or fully homopolymerized or copolymerized in an autoclave or tubular reactor at pressures in excess of 14,500 psi (100 MPa) using a free radical initiator, such as peroxide (see, for example, U.S. Pat. No. 4,599,392, incorporated herein by reference). LDPE resins typically have a viscosity of 0.916 to 0.935 g / cm. 3 The density is in the range of

[0015] The term "LLDPE" includes both resins made using single-site catalysts, including, but not limited to, traditional Ziegler-Natta catalyst systems and chromium-based catalysts, as well as mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes) and constrained geometry catalysts, phosphinimine catalysts and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy), and includes linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. LLDPE contains less long chain branching than LDPE and includes substantially linear ethylene polymers as further defined in U.S. Patent Nos. 5,272,236, 5,278,272, 5,582,923, and 5,733,155, homogeneously branched linear ethylene polymer compositions such as those in U.S. Patent No. 3,645,992, heterogeneously branched ethylene polymers such as those prepared according to the process disclosed in U.S. Patent No. 4,076,698, and / or blends thereof (such as those disclosed in U.S. Patent No. 3,914,342 or U.S. Patent No. 5,854,045). LLDPE may be made via gas phase, solution phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.

[0016] The term "MDPE" means 0.924 to 0.936 g / cm 3"MDPE" refers to polyethylene having a density of 100 to 2000 nm. "MDPE" is typically made using chromium or Ziegler-Natta catalysts, or using single-site catalysts, including, but not limited to, substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy).

[0017] The term "HDPE" refers to poly(ethylene glycol) having a viscosity of about 0.935 g / cm, typically prepared using single-site catalysts including, but not limited to, Ziegler-Natta, chromium, or substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy). 3 Super ~ maximum approx. 0.980g / cm 3 It refers to polyethylene having a density of

[0018] The term "ULDPE" refers to poly(ethylene glycol) copolymers (ULDPE) having a viscosity of 0.855 to 0.912 g / cm, typically prepared using single-site catalysts including, but not limited to, Ziegler-Natta, chromium, or substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy). 3 ULDPE refers to polyethylene having a density of 0.855 to 0.912 g / cm. Examples of ULDPE include, but are not limited to, polyethylene (ethylene-based) plastomers and polyethylene (ethylene-based) elastomers. Polyethylene (ethylene-based) elastomers or plastomers generally have a density of 0.855 to 0.912 g / cm. 3 has a density of

[0019] The terms "blend", "polymer blend" and the like refer to a composition of two or more polymers. Such blends may or may not be miscible. Such blends may or may not be phase separated. Such blends may or may not contain one or more domain configurations as determined from transmission electron spectroscopy, light scattering, X-ray scattering, and any other method known in the art. A blend is not a laminate, although one or more layers of a laminate may contain the blend. Such blends may be prepared as dry blends formed in situ (e.g., in a reactor), as melt blends, or using other techniques known to those skilled in the art.

[0020] Unless stated to the contrary, implied from the context, or customary in the art, all parts and percentages are by weight, all temperatures are in degrees Celsius, and all test methods are current as of the filing date of this disclosure.

[0021] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of any doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless otherwise stated to the contrary. The term "consisting of" excludes any component, step, or procedure not specifically delineated or listed.

[0022] Polyethylene composition and characterization

[0023] In one or more embodiments, the polyethylene composition has a viscosity of 0.880 g / cm 3 ~0.910g / cm 3 For example, an embodiment of the polyethylene composition of the present disclosure may have a density of 0.880 g / cm3 ~0.908g / cm 3 , 0.880g / cm 3 ~0.906g / cm 3 , 0.880g / cm 3 ~0.904g / cm 3 , 0.880g / cm 3 ~0.902g / cm 3 , 0.880g / cm 3 ~0.900g / cm 3 , 0.900g / cm 3 ~0.908g / cm 3 , 0.900g / cm 3 ~0.906g / cm 3 , 0.900g / cm 3 ~0.904g / cm 3 , 0.900g / cm 3 ~0.902g / cm 3 , 0.902g / cm 3 ~0.910g / cm 3 , 0.902g / cm 3 ~0.908g / cm 3 , 0.902g / cm 3 ~0.906g / cm 3 , 0.902g / cm 3 ~0.904g / cm 3 , 0.904g / cm 3 ~0.910g / cm 3 , 0.904g / cm 3 ~0.908g / cm 3 , 0.904g / cm 3 ~0.906g / cm 3 , 0.906g / cm 3 ~0.910g / cm 3 , 0.906g / cm 3 ~0.908g / cm 3 , 0.908g / cm 3 ~0.910g / cm 3 , or any combination of these ranges.

[0024] In one or more embodiments, the polyethylene composition may have a melt index (I2) of 0.50 g / 10 min to 6.0 g / 10 min. For example, in one or more embodiments, the polyethylene composition may have a melt index (I2) of 0.5 g / 10 min to 5.0 g / 10 min, 0.5 g / 10 min to 4.0 g / 10 min, 0.5 g / 10 min to 3.0 g / 10 min, 0.5 g / 10 min to 2.0 g / 10 min, 0.5 g / 10 min to 1.0 g / 10 min, 1.0 g / 10 min to 6.0 g / 10 min, 1.0 g / 10 min to 5.0 g / 10 min, 1.0 g / 10 min to 4.0 g / 10 min, 1.0 g / 10 min to 3.0 g / 10 min, 1.0 g / 10 min to 2.0 g / 10 min, 2.0 g / The melt index (I2) may be from 10 min to 6.0 g / 10 min, 2.0 g / 10 min to 5.0 g / 10 min, 2.0 g / 10 min to 4.0 g / 10 min, 2.0 g / 10 min to 3.0 g / 10 min, 3.0 g / 10 min to 6.0 g / 10 min, 3.0 g / 10 min to 5.0 g / 10 min, 3.0 g / 10 min to 4.0 g / 10 min, 4.0 g / 10 min to 6.0 g / 10 min, 4.0 g / 10 min to 5.0 g / 10 min, 5.0 g / 10 min to 6.0 g / 10 min, or any combination of these ranges.

[0025] According to an embodiment, the polyethylene composition may have a molecular weight distribution, expressed as the ratio of weight average molecular weight to number average molecular weight (Mw / Mn), in the range of 2.0 to 6.0. For example, the polyethylene composition may have a molecular weight distribution of 2.0 to 5.5, 2.0 to 5.0, 2.0 to 4.5, 2.0 to 4.0, 2.0 to 3.5, 2.0 to 3.0, 2.0 to 2.5, 2.5 to 6.0, 3.0 to 5.5, 3.0 to 5.0, 3.0 to 4.5, 3.0 to 4.0, 3.0 to 3.5, 3.5 to 6.0, 3.5 to 5.5, 3.5 to 5.0, 3.5 to 4.5, 3.5 to 4.0, 4.0 to 6.0, 4.0 to 5.5, 4.0 to 5.0, 4.0 to 4.5, 4.5 to 6.0, 4.5 to 5.5, 4.5 to 5.0, 5.0 to 6.0, 5.0 to 5.5, or 5.5 to 6.0, or any combination of these ranges. As described herein, the molecular weight distribution may be calculated according to gel permeation chromatography (GPC) techniques as described herein.

[0026] According to one or more additional embodiments, the polyethylene composition may have a zero shear viscosity ratio of less than 2.0. For example, the polyethylene composition may have a zero shear viscosity ratio of less than 1.9, less than 1.8, less than 1.7, less than 1.6, less than 1.5, less than 1.4, less than 1.3, less than 1.2, or even less than 1.1. In one or more embodiments, the polyethylene composition may have a zero shear viscosity ratio of at least 1.0. In embodiments, the polyethylene composition may have a zero shear viscosity ratio of 1.0-2.0, 1.0-1.8, 1.0-1.6, 1.0-1.4, 1.0-1.2, 1.2-2.0, 1.2-1.8, 1.2-1.6, 1.2-1.4, 1.4-2.0, 1.4-1.8, 1.4-1.6, 1.6-2.0, 1.6-1.8, or 1.8-2.0.

[0027] Tan delta (tan δ) refers to a measure of how close a material is to a perfect elastic solid (d=0°, tan delta=0) or a perfect Newtonian liquid (d=90°, tan delta≈infinite). Thus, lower values ​​of tan d reflect greater elasticity. Tan delta is a function of long chain branching (LCB) and molecular weight distribution (MWD) at the same overall molecular weight. Higher tan delta values ​​indicate lower LCB. In an embodiment, the polyethylene composition is 10-100, 10-90, 10-80, 10-70, 10-60, 10-50, 10-40, 10-30, 10-20, 20-100, 20-90, 20-80, 20-70, 20-60, 20-50, 20-40, 20-30, 30-100, 30-90, 30-80, 30-70, 30-60, 30-50, 30-40 It may have a tan delta at 0.1 radians / sec and 190° C. of 0, 40-100, 40-90, 40-80, 40-70, 40-60, 40-50, 50-100, 50-90, 50-80, 50-70, 50-60, 60-100, 60-90, 60-80, 60-70, 70-100, 70-90, 70-80, 80-100, 80-90, or 90-100.

[0028] As described herein, a polyethylene "fraction" refers to a portion of the overall composition of a polyethylene composition. An embodiment of the present disclosure may include at least a "first polyethylene fraction" and a "second polyethylene fraction." An embodiment may include a "third polyethylene fraction" and a "fourth polyethylene fraction." The various fractions contained within the polyethylene composition may be defined by their temperature ranges in an elution profile via an improved comonomer composition distribution (iCCD) analysis method. For example, a polyethylene fraction may be defined by a range from a lower temperature to a higher temperature. It is understood that two or more polyethylene fractions may overlap with one another. A polyethylene fraction may generally correlate, in one or more embodiments, with a peak or trough in the iCCD data. In one or more embodiments, a particular polyethylene fraction may comprise a specified percentage of the total area of ​​the polyethylene composition as defined by the iCCD analysis elution profile. Unless otherwise specified, any elution profile referred to herein is an elution profile observed via iCCD. Examples of such fractions will be better understood in view of the examples provided herein.

[0029] In general, the first fraction may include at least one peak within the temperature range of the first fraction. The second fraction may include at least one peak within the temperature range of the second fraction. The fourth fraction may include at least one peak within the temperature range of the fourth fraction. The polyethylene compositions described herein may be referred to as "multimodal", meaning that the polyethylene compositions include at least two peaks in their elution profile. In embodiments, the polyethylene compositions described herein may include two peaks ("bimodal"), three peaks ("trimodal"), or four or more peaks in their elution profile. The first polyethylene area fraction, the second polyethylene fraction, the third polyethylene fraction, and the fourth polyethylene fraction each may comprise a portion of the total mass of the polyethylene composition.

[0030] In relation to the iCCD distributions described, Figure 1 illustrates generally an exemplary iCCD distribution 100. Figure 1 illustrates several features of the iCCD profiles of the polyethylene compositions described herein, such as the first fraction, second fraction, third fraction, fourth fraction, etc., discussed in detail herein. Thus, Figure 1 may be used as a reference with respect to the disclosure related to iCCD profiles provided herein.

[0031] Specifically shown are a first fraction 102, a second fraction 104, a third fraction 106, and a fourth fraction 108. The first fraction 102 has a peak 112, and the second fraction 104 has a peak 114. The fourth fraction 108 may have a peak 118. It should be understood that the profile in Figure 1 is not derived from experiment or observation, but instead is provided for informational purposes to describe certain features of iCCD elution profiles.

[0032] In one or more embodiments, one or more of the first polyethylene fraction, the second polyethylene fraction, and the fourth polyethylene fraction may have a single peak. As used herein, "single peak" refers to an iCCD in which a particular fraction contains only a single peak. That is, in some embodiments, an iCCD in one or more of the first polyethylene fraction, the second polyethylene fraction, and the fourth polyethylene fraction contains only a downward sloping region followed by an upward sloping region to form a single peak.

[0033] It should be understood that the peaks in one or more of the first polyethylene fraction, the second polyethylene fraction, and the fourth polyethylene fraction may not be formed by a local minimum in the respective polyethylene fraction at a defined temperature boundary. That is, the peaks must be peaks in terms of their entire range, rather than peaks formed by a threshold temperature of the polyethylene fraction. For example, if a polyethylene fraction has a single peak followed by a single valley (an upward slope followed by a downward slope followed by an upward slope), then there will be only a single peak in such polyethylene fraction.

[0034] In one or more embodiments, the first polyethylene fraction 102 can be the area in an elution profile from 35° C. to 70° C. In additional embodiments, the first polyethylene fraction 102 can be the area in an elution profile within the temperature ranges of 35° C. to 60° C., 35° C. to 50° C., 40° C. to 70° C., 40° C. to 60° C., 40° C. to 50° C., 50° C. to 70° C., 50° C. to 60° C., 60° C. to 70° C., or any combination thereof, in an elution profile via an iCCD.

[0035] According to one or more embodiments, the first polyethylene fraction area may comprise at least 25% of the total area of ​​the elution profile (e.g., at least 30%, at least 40%, at least 50%, or even at least 60% of the total area of ​​the elution profile). For example, the first polyethylene fraction area may comprise between 25% and 65%, between 25% and 55%, between 25% and 45%, between 25% and 35%, between 35% and 65%, between 35% and 55%, between 35% and 45%, between 45% and 65%, between 45% and 55%, between 55% and 65%, or any combination of the total area of ​​the elution profile.

[0036] In one or more embodiments, the first polyethylene fraction 102 may have at least one peak 112 in an elution profile via iCCD in a temperature range of 35° C. to 70° C. In one or more embodiments, the first polyethylene fraction 102 may have at least one peak 112 in an elution profile via iCCD in a temperature range of 35° C. to 60° C., 35° C. to 50° C., 40° C. to 70° C., 40° C. to 60° C., 40° C. to 50° C., 50° C. to 70° C., 50° C. to 60° C., 60° C. to 70° C., or any combination thereof.

[0037] A temperature range of the first polyethylene fraction from 35° C. to 70° C. may be desirable since it may correspond to a low density component of the polyethylene composition. In embodiments, the low density component may provide a low hot tack initiation temperature, heat seal initiation temperature, or both. Thus, by increasing the first polyethylene fraction 102, which may include a low density component, the hot tack initiation temperature, heat seal initiation temperature, or both of the polyethylene composition may be reduced, improving the hot tack strength and hot tack window.

[0038] In one or more embodiments, the second polyethylene fraction 104 can be the area in an elution profile from 85° C. to 120° C. In additional embodiments, the second polyethylene fraction 104 can be the area in an elution profile within the temperature ranges of 85° C. to 110° C., 85° C. to 100° C., 85° C. to 90° C., 90° C. to 120° C., 90° C. to 110° C., 90° C. to 100° C., 100° C. to 120° C., 100° C. to 110° C., 110° C. to 120° C., or any combination thereof, in an elution profile via an iCCD.

[0039] According to one or more embodiments, the second polyethylene fraction area may comprise at least 20% of the total area of ​​the elution profile (e.g., at least 30%, at least 35%, at least 40%, or at least 45% of the total area of ​​the elution profile). For example, the second polyethylene fraction area may comprise 20%-60%, 20%-50%, 20%-40%, 20%-30%, 30%-60%, 30%-50%, 30%-40%, 40%-60%, 40%-50%, 50%-60%, or any combination of the total area of ​​the elution profile.

[0040] In one or more embodiments, the second polyethylene fraction 104 may have at least one peak 114 in an elution profile via iCCD in a temperature range of 85° C. to 120° C. In one or more embodiments, the second polyethylene fraction 104 may have at least one peak 114 in an elution profile via iCCD in a temperature range of 85° C. to 110° C., 85° C. to 100° C., 85° C. to 90° C., 90° C. to 120° C., 90° C. to 110° C., 90° C. to 100° C., 100° C. to 120° C., 100° C. to 110° C., 110° C. to 120° C., or any combination thereof.

[0041] A temperature range of the second polyethylene fraction between 85°C and 120°C may be desirable since it may accommodate the high density component. In an embodiment, increasing the high density component may increase the overall density of the polyethylene composition. Thus, increasing the second polyethylene fraction 104 may increase the high density component and provide a polyethylene composition with a higher overall density. In addition, increasing the second polyethylene fraction 104 may improve the blocking properties of the polyethylene composition. Without being bound by theory, it is believed that larger crystals form in the high density fraction, providing a rough surface. The rough surface may reduce the contact area and therefore improve the blocking properties of the polyethylene composition.

[0042] In one or more embodiments, the polyethylene composition may have a minimum in an iCCD-mediated elution profile within the temperature range of 65° C. to 85° C. The minimum may be located between peak 112 of the first polyethylene fraction 102 and peak 114 of the second polyethylene fraction 104.

[0043] In one or more embodiments, the third polyethylene area fraction 106 can be the area in an elution profile between 70° C. and 85° C. In additional embodiments, the third polyethylene fraction 106 can be the area in an elution profile within the temperature ranges of 70° C. to 80° C., 70° C. to 75° C., 75° C. to 85° C., 75° C. to 80° C., 80° C. to 85° C., or any combination of temperatures in an elution profile via an iCCD.

[0044] According to one or more embodiments, the third polyethylene fraction area may comprise less than 10% of the total area of ​​the elution profile (e.g., less than 8%, less than 6%, or less than 4% of the total area of ​​the elution profile). For example, the third polyethylene fraction area may comprise between 4% and 10%, between 4% and 8%, between 4% and 6%, between 6% and 10%, between 6% and 8%, between 8% and 10%, or any combination of the total area of ​​the elution profile.

[0045] In embodiments described herein, the third polyethylene area fraction 106 can be the area in an elution profile from 70° C. to 85° C. In one or more embodiments, the third polyethylene area fraction 106 can be the area in an elution profile from 70° C. to 85° C., 70° C. to 80° C., 70° C. to 75° C., 75° C. to 85° C., 75° C. to 80° C., 80° C. to 85° C., or any combination of elution profiles via an iCCD.

[0046] It may be desirable to minimize the third polyethylene fraction 106 within the temperature range of 70° C. to 85° C., which would otherwise shift the higher density components from the second polyethylene fraction 104 towards a lower temperature range in the elution profile. Without wishing to be bound by theory, it is believed that shifting the higher density components towards a lower temperature range in the elution profile may prevent the polyethylene composition from achieving the desired blocking properties.

[0047] In one or more embodiments, the fourth polyethylene area fraction 108 can be the area in an elution profile from 20° C. to 35° C. In additional embodiments, the fourth polyethylene fraction 104 can be the area in an elution profile within the temperature ranges of 20° C. to 30° C., 20° C. to 25° C., 25° C. to 35° C., 25° C. to 30° C., 30° C. to 35° C., or any combination of temperatures in an elution profile via an iCCD.

[0048] According to one or more embodiments, the fourth polyethylene fraction area may comprise less than 35% of the total area of ​​the elution profile (e.g., less than 30%, less than 20%, less than 10%, less than 5%, or even less than 2% of the total area of ​​the elution profile). For example, the fourth polyethylene fraction area may comprise 0%-35%, 0%-20%, 0%-10%, 0%-5%, 5%-35%, 5%-20%, 5%-10%, 10%-35%, 10%-20%, 20%-35%, or any combination of the total area of ​​the elution profile.

[0049] In embodiments described herein, the fourth polyethylene area fraction 108 is the area in the elution profile under at least one peak 118 of the fourth polyethylene fraction 108 between 20° C. and 35° C. In one or more embodiments, the fourth polyethylene fraction 108 may have at least one peak 118 in the temperature range of 20° C. to 30° C., 20° C. to 25° C., 25° C. to 35° C., 25° C. to 30° C., 30° C. to 35° C., or any combination, in the elution profile via iCCD.

[0050] It may be desirable to minimize the fourth polyethylene fraction 108 within the temperature range of 20° C. to 35° C. Without being bound by theory, it is believed that high amounts of the fourth polyethylene fraction 108 may prevent the polyethylene composition from achieving the desired blocking properties.

[0051] In one or more embodiments, the polyethylene composition may have a minimum in an iCCD-mediated elution profile within a temperature range of 30° C. to 40° C. The minimum may be located between peak 118 of the fourth polyethylene fraction 108 and peak 112 of the first polyethylene fraction 102.

[0052] It should be understood that two or more polyethylene area fractions may overlap one another. In one or more embodiments, the first polyethylene area fraction 102 and the fourth polyethylene area fraction 108 may overlap.

[0053] In one or more embodiments, the polyethylene composition is formed from the polymerization of ethylene and a comonomer, such as a C3-C12 alkene. Contemplated comonomers include C6-C9 alkenes, such as 1-octene and 1-hexene. In one or more embodiments, the comonomer is 1-octene.

[0054] In one or more embodiments, the weight average molecular weight of the first polyethylene fraction can be less than or equal to 225,000 g / mol, such as from 30,000 g / mol to 225,000 g / mol, from 60,000 g / mol to 150,000 g / mol, or from 90,000 g / mol to 120,000 g / mol, or any combination of ranges thereof. The molecular weight of the polyethylene fraction can be calculated based on iCCD results, as described below.

[0055] In one or more embodiments, the weight average molecular weight of the second polyethylene fraction can be less than or equal to 225,000 g / mol, such as from 25,000 g / mol to 225,000 g / mol, from 50,000 g / mol to 150,000 g / mol, or from 75,000 g / mol to 125,000 g / mol, or any combination of ranges thereof. The molecular weight of the polyethylene fraction can be calculated based on iCCD results, as described below.

[0056] In one or more embodiments, the polyethylene composition of the present disclosure may further comprise additional components such as one or more additives. Such additives include, but are not limited to, antistatic agents, color enhancers, dyes, lubricants, fillers such as TiO2 or CaCO3, opacifiers, nucleating agents, processing aids, pigments, primary antioxidants, secondary antioxidants, UV stabilizers, antiblocking agents, slip agents, tackifiers, flame retardants, antimicrobial agents, odor reducing agents, antifungal agents, and combinations thereof. The polyethylene composition may contain from about 0.1 to about 10 weight percent of such additives by combined weight, based on the weight of the polyethylene composition including such additives.

[0057] In an embodiment, the ratio of the molecular weight of the first polyethylene area fraction to the molecular weight of the total area of ​​the elution profile is between 0.5 and 1.5. In an embodiment, the ratio may be between 0.5 and 1.5, between 0.5 and 1.0, or between 1.0 and 1.5.

[0058] polymerization

[0059] Any conventional polymerization process may be used to produce the polyethylene compositions described herein. Such conventional polymerization processes include, but are not limited to, gas phase polymerization processes, slurry polymerization processes, solution polymerization processes using one or more conventional reactors, such as loop reactors, isothermal reactors, stirred tank reactors, pipe flow reactors, plug flow reactors, parallel, serial batch reactors, and / or any combination thereof. The polyethylene compositions may be produced, for example, via a solution phase polymerization process using one or more loop reactors, isothermal reactors, and combinations thereof.

[0060] Generally, the solution phase polymerization process may be carried out in one or more well-mixed reactors, such as one or more isothermal loop reactors or one or more adiabatic reactors, at temperatures in the range of 115°C to 250°C (e.g., 115°C to 210°C) and pressures in the range of 300 psi to 3,000 psi (e.g., 400 psi to 800 psi). In some embodiments, in a dual reactor, the temperature in the first reactor is in the range of 115°C to 190°C (e.g., 150°C to 180°C) and the temperature in the second reactor is in the range of 150°C to 250°C (e.g., 180°C to 220°C). In other embodiments, in a single reactor, the temperature in the reactor is in the range of 115°C to 250°C (e.g., 115°C to 225°C).

[0061] The residence time in the solution phase polymerization process can be in the range of 2 minutes to 30 minutes (e.g., 5 minutes to 25 minutes). Ethylene, solvent, hydrogen, one or more catalyst systems, optionally one or more cocatalysts, and optionally one or more comonomers are continuously fed to one or more reactors. Exemplary solvents include, but are not limited to, isoparaffins. For example, such solvents are commercially available under the name ISOPAR E from ExxonMobil Chemical Co. (Houston, Texas). The resulting mixture of polyethylene composition and solvent is then removed from the reactor and the polyethylene composition is isolated. The solvent is typically recovered via a solvent recovery unit, such as a heat exchanger and a gas-liquid separator drum, and then recycled to the polymerization system.

[0062] In some embodiments, the polyethylene composition may be produced via solution polymerization in a dual reactor system, e.g., a dual loop reactor system, where ethylene is polymerized in the presence of one or more catalyst systems and one or more comonomers. In some embodiments, only ethylene is polymerized. In addition, one or more cocatalysts may be present. In another embodiment, the polyethylene composition may be produced via solution polymerization in a single reactor system, e.g., a single loop reactor system, where ethylene is polymerized in the presence of two catalyst systems and one or more comonomers.

[0063] Catalyst system

[0064] Described herein are specific embodiments of catalyst systems that may be used in one or more embodiments to produce the polyethylene compositions described herein. It is understood that the catalyst systems of the present disclosure may be embodied in different forms and should not be construed as limited to the specific embodiments described in the present disclosure. Rather, the embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the subject matter to those skilled in the art. Without wishing to be bound by theory, the catalyst system may produce a mixture of low density components in a temperature range of 35°C to 70°C, thus enabling the polyethylene composition to achieve the desired hot tack initiation temperature, heat seal initiation temperature, or both, and high density components in a temperature range of 35°C to 70°C, thus enabling the polyethylene composition to achieve the desired blocking properties.

[0065] The term "independently selected" means 1 , R 2 , R 3 , R 4 , and R 5 The R groups, such as, can be the same or different (e.g., R 1 , R 2 , R 3 , R 4 , and R 5 may all be substituted alkyl, or R 1 and R 2 may be substituted alkyl, R 3 The terms "aryl" and "aryl" are used herein to indicate that the term "aryl" refers to a group of atoms that are aryl, etc. The use of the singular includes the use of the plural and vice versa (e.g., a hexane solvent includes a plurality of hexanes). A named R group will generally have a structure recognized in the art as corresponding to the R group with that name. These definitions are intended to supplement and illustrate, not preclude, definitions known to those of skill in the art.

[0066] The term "procatalyst" refers to a compound that has catalytic activity when combined with an activator. The term "activator" refers to a compound that chemically reacts with a procatalyst in a manner that converts the procatalyst into a catalytically active catalyst. As used herein, the terms "cocatalyst" and "activator" are interchangeable terms.

[0067] When used to describe certain carbon atom-containing chemical groups, "(C x ~C y A bracketed expression having the form "(C1-C)" means that the unsubstituted form of the chemical group has x carbon atoms to y carbon atoms, inclusive of x and y. For example, (C1-C 40 ) Alkyl is an alkyl group having 1 to 40 carbon atoms in its unsubstituted form. In some embodiments and general structures, specific chemical groups include R S The parenthetical "(C x ~C y ) for chemical groups defined using S The substituted version is an arbitrary group R S Depending on the identity of R, R may contain more than y carbon atoms. For example, S Exactly one group R is phenyl (-C6H5) S (C1~C 40 "(C)alkyl" can contain from 7 to 46 carbon atoms. Thus, the parenthetical "(C)alkyl" is generally used. x ~C y ) is a group defined using one or more carbon atom-containing substituents R S When substituted by, the minimum and maximum total number of carbon atoms in the chemical group shall be determined by the sum of all carbon atom-containing substituents R S The total number of carbon atoms from the alkyl group is determined by adding the total number of carbon atoms from the alkyl group.

[0068] The term “substituted” refers to the replacement of at least one hydrogen atom (—H) bonded to a carbon or heteroatom of a corresponding unsubstituted compound or functional group with a substituent (e.g., R SThe term "persubstituted" means that all hydrogen atoms (H) bonded to carbon or heteroatoms of the corresponding unsubstituted compound or functional group are replaced by a substituent (e.g., R S The term "polysubstituted" means that at least two, but fewer than all, of the hydrogen atoms bonded to a carbon atom or heteroatom of the corresponding unsubstituted compound or functional group are replaced by a substituent.

[0069] The term "-H" means a hydrogen or hydrogen radical covalently bonded to another atom. "Hydrogen" and "-H" are interchangeable and mean the same thing unless otherwise specified.

[0070] "(C1~C 40 The term "(C1-C)hydrocarbyl" means a hydrocarbon radical of 1 to 40 carbon atoms. 40 The term "hydrocarbylene" means a hydrocarbon diradical of 1 to 40 carbon atoms, each of which may be aromatic or non-aromatic, saturated or unsaturated, straight or branched chain, cyclic (monocyclic and polycyclic, fused and non-fused polycyclic, including bicyclic, containing 3 or more carbon atoms) or acyclic, unsubstituted or substituted with one or more R S has been replaced by

[0071] In the present disclosure, (C1 to C 40 ) Hydrocarbyl is unsubstituted or substituted (C1-C 40 ) Alkyl, (C3-C 40 )Cycloalkyl, (C3-C 20 )Cycloalkyl-(C1-C 20 ) Alkylene, (C6-C 40 ) aryl, or (C6-C 20 )Aryl-(C1-C 20 In some embodiments, the aforementioned (C1-C 40 Each of the hydrocarbyl groups has up to 20 carbon atoms (i.e., (C1-C 20) hydrocarbyl), in other embodiments having up to 12 carbon atoms.

[0072] "(C1~C 40 ) alkyl" and "(C1-C 18 The terms "alkyl" and "alkyl-alkyl" refer to groups that are unsubstituted or have one or more R S means a saturated linear or branched hydrocarbon radical of 1 to 40 carbon atoms or 1 to 18 carbon atoms substituted by unsubstituted (C1 to C 40 Examples of alkyl are unsubstituted (C1-C 20 ) Alkyl, unsubstituted (C1-C 10 ) alkyl, unsubstituted (C1-C5) alkyl, methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-butyl, 2-methylpropyl, 1,1-dimethylethyl, 1-pentyl, 1-hexyl, 1-heptyl, 1-nonyl, and 1-decyl. 40 Examples of substituted (C1-C 20 ) Alkyl, Substituted (C1-C 10 ) alkyl, trifluoromethyl, and [C 45 ] alkyl. 45 The term "alkyl" (with brackets) means that there are up to 45 carbon atoms in the radical, including the substituents, e.g., one R that is (C1-C5) alkyl, S Replaced by (C 27 ~C 40 )alkyl. Each (C1-C5)alkyl can be methyl, trifluoromethyl, ethyl, 1-propyl, 1-methylethyl, or 1,1-dimethylethyl.

[0073] "(C6~C 40 The term "aryl" refers to unsubstituted or substituted (one or more R Smeans a monocyclic, bicyclic, or tricyclic aromatic hydrocarbon radical, of which at least 6 to 14 carbon atoms are aromatic ring carbon atoms, the monocyclic, bicyclic, or tricyclic radical containing 1, 2, or 3 rings, respectively, one ring being aromatic and two or three rings being independently fused or non-fused, and at least one of the two or three rings being aromatic. 40 Examples of aryl are unsubstituted (C6-C 20 )Aryl, unsubstituted (C6-C 18 )aryl, (C1-C5)alkyl-phenyl, 2,4-bis(C1-C5)alkyl-phenyl, phenyl, fluorenyl, tetrahydrofluorenyl, indacenyl, hexahydroindacenyl, indenyl, dihydroindenyl, naphthyl, tetrahydronaphthyl, and phenanthrene. 40 Examples of aryl are substituted (C1-C 20 )Aryl, Substituted (C6-C 18 )aryl, 2,4-bis[(C 20 ) alkyl]-phenyl, polyfluorophenyl, pentafluorophenyl, and fluoren-9-on-1-yl.

[0074] "(C3~C 40 The term "cycloalkyl" means unsubstituted or substituted with one or more R S means a saturated cyclic hydrocarbon radical of 3 to 40 carbon atoms, substituted with other cycloalkyl groups, such as (C x ~C y )Cycloalkyl) has x to y carbon atoms and is unsubstituted or has one or more R S Unsubstituted (C3-C 40 Examples of cycloalkyl are unsubstituted (C3-C 20 )Cycloalkyl, unsubstituted (C3-C 10 ) cycloalkyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, and cyclodecyl. 40Examples of cycloalkyl are substituted (C3-C 20 )Cycloalkyl, substituted (C3-C 10 ) cycloalkyl, cyclopentanon-2-yl, and 1-fluorocyclohexyl.

[0075] (C1~C 40 Examples of hydrocarbylenes include unsubstituted or substituted (C6-C 40 )Arylene, (C3-C 40 ) cycloalkylene, and (C1-C 40 ) alkylene (e.g., (C1-C 20 ) alkylene). In some embodiments, the diradicals are on the same carbon atom (e.g., -CH2-), or on adjacent carbon atoms (i.e., 1,2-diradicals), or separated by one, two, or more intervening carbon atoms (e.g., 1,3-diradicals, 1,4-diradicals, etc.). Some diradicals include α,ω-diradicals. α,ω-diradicals are diradicals with the greatest carbon backbone spacing between the radical carbons. (C2-C 20 Some examples of alkylene α,ω-diradicals include ethane-1,2-diyl (i.e., -CH2CH2-), propane-1,3-diyl (i.e., -CH2CH2CH2-), 2-methylpropane-1,3-diyl (i.e., -CH2CH(CH3)CH2-). (C6-C 50 ) Some examples of arylene α,ω-diradicals include phenyl-1,4-diyl, naphthalene-2,6-diyl, or naphthalene-3,7-diyl.

[0076] "(C1~C 40 The term "alkylene" may be unsubstituted or may contain one or more R S means a saturated straight or branched diradical of 1 to 40 carbon atoms (i.e., the radical is not on a ring atom) substituted by 50Examples of alkylene are unsubstituted -CH2CH2-, -(CH2)3-, -(CH2)4-, -(CH2)5-, -(CH2)6-, -(CH2)7-, -(CH2)8-, -CH2C * HCH3 and -(CH2)4C * (H)(CH3) and unsubstituted (C1-C 20 ) alkylene, * " denotes a carbon atom from which a hydrogen atom has been removed to form a secondary or tertiary alkyl radical. 50 Examples of alkylene are substituted (C1-C 20 ) alkylene, -CF2-, -C(O)-, and -(CH2) 14 C(CH3)2(CH2)5- (i.e., 6,6-dimethyl-substituted normal-1,20-eicosylene). As mentioned above, the two R S Together, (C1~C 18 ) alkylene, 50 Examples of alkylenes include 1,2-bis(methylene)cyclopentane, 1,2-bis(methylene)cyclohexane, 2,3-bis(methylene)-7,7-dimethyl-bicyclo[2.2.1]heptane, and 2,3-bis(methylene)bicyclo[2.2.2]octane.

[0077] "(C3~C 40 The term "cycloalkylene" may be unsubstituted or may contain one or more R S "R" means a cyclic diradical (i.e., the radicals are on ring atoms) of 3 to 40 carbon atoms substituted by

[0078] The term "heteroatom" refers to an atom other than hydrogen or carbon. Examples of heteroatoms include O, S, S(O), S(O), Si(R C )2, P(R P ), N(R N ), -N=C(R C )2, -Ge(R C )2-, or -Si(R C )-, and each R C , each R N , and each RP is unsubstituted (C1 to C 18 ) hydrocarbyl or -H. The term "heterohydrocarbon" refers to a molecule or molecular skeleton in which one or more carbon atoms are replaced with a heteroatom. 40 The term "heterohydrocarbyl" means a heterohydrocarbon radical of 1 to 40 carbon atoms, and is used interchangeably with "(C1-C 40 The term "heterohydrocarbylene" means a heterohydrocarbon diradical of 1 to 40 carbon atoms, each heterohydrocarbon having one or more heteroatoms. The heterohydrocarbyl radical can be on a carbon atom or a heteroatom, and the heterohydrocarbyl diradical can be on (1) 1 or 2 carbon atoms, (2) 1 or 2 heteroatoms, or (3) 1 carbon atom and 1 heteroatom. Each (C1 to C 50 ) heterohydrocarbyl and (C1-C 50 ) Heterohydrocarbylene is unsubstituted or (one or more R S They may be substituted (by) and may be aromatic or non-aromatic, saturated or unsaturated, straight or branched chain, cyclic (including monocyclic and polycyclic, fused and non-fused polycyclic) or acyclic.

[0079] (C1~C 40 ) Heterohydrocarbyl is unsubstituted or substituted (C1-C 40 )heteroalkyl, (C1-C 40 ) hydrocarbyl-O-, (C1-C 40 ) Hydrocarbyl-S-, (C1-C 40 ) hydrocarbyl-S(O)-, (C1-C 40 ) hydrocarbyl-S(O)2-, (C1-C 40 ) Hydrocarbyl-Si(R C )2-, (C l ~C 40 )hydrocarbyl-N(R N )-, (C l ~C 40 ) hydrocarbyl-P(R P )-, (C2~C 40 )heterocycloalkyl, (C2-C 19 )Heterocycloalkyl-(C1-C20 ) alkylene, (C3-C 20 )Cycloalkyl-(C1-C 19 ) Heteroalkylene, (C2-C 19 )Heterocycloalkyl-(C1-C 20 ) Heteroalkylene, (C1-C 40 ) Heteroaryl, (C1-C 19 )Heteroaryl-(C1-C 20 ) Alkylene, (C6-C 20 )Aryl-(C1-C 19 ) heteroalkylene, or (C1-C 19 )Heteroaryl-(C1-C 20 ) heteroalkylene.

[0080] "(C3~C 40 The term "heteroaryl" refers to an unsubstituted or substituted heteroaryl group consisting of 4 to 40 total carbon atoms and 1 to 10 heteroatoms (one or more R S (C4-C6) means a monocyclic, bicyclic, or tricyclic heteroaromatic hydrocarbon radical, the monocyclic, bicyclic, or tricyclic radical containing 1, 2, or 3 rings, respectively, the 2 or 3 rings being independently fused or non-fused, and at least one of the 2 or 3 rings being heteroaromatic. Other heteroaryl groups (e.g., (C4-C6) 12 )heteroaryl, etc. x -C y ) Heteroaryl (general) has x to y carbon atoms (e.g., 4 to 12 carbon atoms) and is unsubstituted or has one or more R SThe monocyclic heteroaromatic hydrocarbon radicals are defined in a similar manner as being substituted with. The monocyclic heteroaromatic hydrocarbon radicals are 5- or 6-membered rings. The 5-membered ring has 5 minus h carbon atoms, where h is the number of heteroatoms, which can be 1, 2, or 3, and each heteroatom can be O, S, N, or P. Examples of 5-membered heteroaromatic hydrocarbon radicals are pyrrol-1-yl, pyrrol-2-yl, furan-3-yl, thiophen-2-yl, pyrazol-1-yl, isoxazol-2-yl, isothiazol-5-yl, imidazol-2-yl, oxazol-4-yl, thiazol-2-yl, 1,2,4-triazol-1-yl, 1,3,4-oxadiazol-2-yl, 1,3,4-thiadiazol-2-yl, tetrazol-1-yl, tetrazol-2-yl, and tetrazol-5-yl. The 6-membered ring has 6 minus h carbon atoms, where h is the number of heteroatoms, which may be 1 or 2, and the heteroatoms may be N or P. Examples of 6-membered heteroaromatic hydrocarbon radicals are pyridin-2-yl, pyrimidin-2-yl, and pyrazin-2-yl. The bicyclic heteroaromatic hydrocarbon radicals may be fused 5,6- or 6,6-ring systems. Examples of fused 5,6-ring bicyclic heteroaromatic hydrocarbon radicals are indol-1-yl and benzimidazol-1-yl. Examples of fused 6,6-ring bicyclic heteroaromatic hydrocarbon radicals are quinolin-2-yl and isoquinolin-1-yl. The tricyclic heteroaromatic hydrocarbon radicals may be fused 5,6,5-, 5,6,6-, 6,5,6-, or 6,6,6-ring systems. An example of a fused 5,6,5-ring system is 1,7-dihydropyrrolo[3,2-f]indol-1-yl. An example of a fused 5,6,6-ring system is 1H-benzo[f]indol-1-yl. An example of a fused 6,5,6-ring system is 9H-carbazol-9-yl. An example of a fused 6,5,6-ring system is 9H-carbazol-9-yl. An example of a fused 6,6,6-ring system is acridine-9-yl.

[0081] The heteroalkyl group is any of (C1-C 50) carbon atoms, or a saturated straight or branched chain radical containing fewer carbon atoms and one or more heteroatoms. Similarly, heteroalkylene can be a saturated straight or branched chain diradical containing 1 to 50 carbon atoms and one or more heteroatoms. Heteroatoms as defined above include Si(R C )3, Ge(R C )3, Si(R C )2, Ge(R C )2, P(R P )2, P(R P ), N(R N )2, N(R N ), N, O, OR C , S, S.R. C , S(O), and S(O), each of the heteroalkyl and heteroalkylene groups can be unsubstituted or can have one or more R S has been replaced by

[0082] Unsubstituted (C2~C 40 Examples of heterocycloalkyl are unsubstituted (C-C 20 )Heterocycloalkyl, unsubstituted (C2-C 10 ) heterocycloalkyl, aziridin-1-yl, oxetan-2-yl, tetrahydrofuran-3-yl, pyrrolidin-1-yl, tetrahydrothiophene-S,S-dioxid-2-yl, morpholin-4-yl, 1,4-dioxan-2-yl, hexahydroazepin-4-yl, 3-oxa-cyclooctyl, 5-thio-cyclononyl, and 2-aza-cyclodecyl.

[0083] The term "halogen atom" or "halogen" refers to a radical of a fluorine atom (F), a chlorine atom (Cl), a bromine atom (Br), or an iodine atom (I). The term "halide" refers to a radical of a fluoride atom (F - ), chloride (Cl - ), bromide (Br - ), or iodide (I - ) refers to the anionic form of a halogen atom.

[0084] The term "saturated" means lacking carbon-carbon double bonds, carbon-carbon triple bonds, and (in heteroatom-containing groups) carbon-nitrogen, carbon-phosphorus, and carbon-silicon double bonds. A saturated chemical group is one or more substituents R S When substituted by, one or more double and / or triple bonds may optionally be replaced by a substituent R S The term "unsaturated" refers to the presence of one or more carbon-carbon double bonds, carbon-carbon triple bonds, and (in heteroatom-containing groups) carbon-nitrogen, carbon-phosphorus, and carbon-silicon double bonds, provided that, if present, the substituent R S It is meant to exclude any double bonds that may be present in or, if present, in a (hetero)aromatic ring.

[0085] According to some embodiments, the catalyst system for producing the polyethylene composition comprises a metal-ligand complex according to formula (I): [ka]

[0086] In formula (I), M is a metal selected from titanium, zirconium, or hafnium, the metal is in a formal oxidation state of +2, +3, or +4, n is 0, 1, or 2, when n is 1, X is a monodentate or bidentate ligand, and when n is 2, each X is a monodentate ligand and may be the same or different, the metal-ligand complex is overall charge neutral, and each Z is independently selected from -O-, -S-, -N(R N )- or -P(R P )-, and L is selected from (C1 to C 40 ) hydrocarbylene or (C1-C 40 ) heterohydrocarbylene, (C1-C 40 ) Hydrocarbylene has a moiety containing a linker skeleton of 1 to 10 carbon atoms connecting the two Z groups in formula (I) (to which L is attached), or 40Heterohydrocarbylene has a moiety containing a linker skeleton of 1 to 10 atoms connecting the two Z groups in formula (I), and (C1 to C 40 Each of the 1 to 10 atoms of the 1 to 10 atom linker backbone of the heterohydrocarbylene is independently a carbon atom or a heteroatom, and each heteroatom is independently O, S, S(O), S(O), Si(R C )2, Ge(R C )2, P(R C ), or N(R C ) and each R C are independently 30 ) hydrocarbyl or (C1-C 30 ) heterohydrocarbyl, R 1 and R 8 are independently -H, (C1 to C 40 ) hydrocarbyl, (C1-C 40 ) heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, -OR C , -SR C , -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R N ) 2NC(O)-, halogen, and a radical having formula (II), formula (III), or formula (IV). [ka]

[0087] In formulas (II), (III), and (IV), R 31~35 , R 41~48 , or R 51~59 Each of the following is independently: 40 ) hydrocarbyl, (C1-C40 ) heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, -N=CHR C , -OR C , -SR C , -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R N ) 2NC(O)-, halogen, or -H, provided that R 1 or R 8 is a radical having formula (II), formula (III), or formula (IV).

[0088] In formula (I), R 2~4 , R 5~7 , and R 9~16 Each of the following is independently: 40 ) hydrocarbyl, (C1-C 40 ) heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, -N=CHR C , -OR C , -SR C , -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R C ) 2NC(O)-, halogen, and -H.

[0089] In some embodiments, the polyethylene composition is formed using a first catalyst according to formula (I) in a first reactor and a different catalyst according to formula (I) in a second reactor.

[0090] In one exemplary embodiment in which a dual loop reactor is used, the procatalyst used in the first loop is zirconium, [[2,2''-[[bis[1-methylethyl]germylene]bis(methyleneoxy-κO)]bis[3'',5,5''-tris(1,1-dimethylethyl)-5'-octyl[1,1':3',1''-terphenyl]-2'-olato-κO]](2-)]dimethyl-, which has the chemical formula C 86 H 128 F2GeO4Zr, and has the following structure (V): [ka]

[0091] In such an embodiment, the procatalyst used in the second loop is zirconium, [[2,2'''-[1,3-propanediylbis(oxy-κO)]bis[3-[2,7-bis(1,1-dimethylethyl)-9H-carbazol-9-yl]]-5'-(dimethyloctylsilyl)-3'-methyl-5-(1,1,3,3-tetramethylbutyl)[1,1]-biphenyl]-2-olato-κO]](2-)]dimethyl, having the chemical formula C 107 H 154 N2O4Si2Zr and has the following structure (VI): [ka]

[0092] In another embodiment, the procatalyst used in the second loop is hafnium, [[2,2'''-[1,3-propanediylbis(oxy-κO)]bis[3-[2,7-bis(1,1-dimethylethyl)-9H-carbazol-9-yl]]-5'-(dimethyloctylsilyl)-3'-methyl-5-(1,1,3,3-tetramethylbutyl)[1,1]-biphenyl]-2-olato-κO]](2-)]dimethyl, having the chemical formula CHNOSiZr and the following structure (VII): [ka]

[0093] Cocatalyst Component

[0094] The catalyst system comprising the metal-ligand complex of formula (I) can be catalytically activated by any technique known in the art for activating metal-based catalysts for olefin polymerization reactions. For example, the system comprising the metal-ligand complex of formula (I) can be catalytically activated by contacting the complex with an activating cocatalyst or combining the complex with an activating cocatalyst. Suitable activating cocatalysts for use herein include alkylaluminum; polymeric or oligomeric alumoxanes (also known as aluminoxanes); neutral Lewis acids; and non-polymeric, non-coordinating, ion-forming compounds (including the use of such compounds under oxidizing conditions). A suitable activation technique is bulk electrolysis. Combinations of one or more of the foregoing activating cocatalysts and techniques are also contemplated. The term "alkylaluminum" means monoalkylaluminum dihydride or dihalide, dialkylaluminum hydride or halide, or trialkylaluminum. Examples of polymeric or oligomeric alumoxanes include methylalumoxane, triisobutylaluminum modified methylalumoxane, and isobutylalumoxane.

[0095] The Lewis acid activator (co-catalyst) may be any of the Lewis acid activators having one to three (C1-C20 In one embodiment, the Group 13 metal compound includes a tri((C1-C) hydrocarbyl substituent. 20 )hydrocarbyl)-substituted-aluminum or tri((C1-C 20 In another embodiment, the Group 13 metal compound is a tri(hydrocarbyl)-substituted aluminum, tri((C1-C 20 )hydrocarbyl)-boron compounds, tri((C1-C 10 ) alkyl) aluminum, tri((C6-C 18 )aryl)boron compounds and their halogenated (including perhalogenated) derivatives. In further embodiments, the Group 13 metal compound is tris(fluoro-substituted phenyl)borane, tris(pentafluorophenyl)borane. In some embodiments, the activating cocatalyst is tris((C1-C 20 ) hydrocarbyl borate (e.g. trityl tetrafluoroborate) or tri((C 20 )hydrocarbyl)ammonium tetra((C1-C 20 )hydrocarbyl)borates (e.g., bis(octadecyl)methylammonium tetrakis(pentafluorophenyl)borate). As used herein, the term "ammonium" refers to any of the (C1-C 20 ) Hydrocarbyl) 4N + , ((C1~C 20 )hydrocarbyl)3N(H) + , ((C1~C 20 )hydrocarbyl)2N(H)2 + , (C1~C 20 ) HydrocarbylN(H)3 + , or N(H)4 + Each of the nitrogen cations (C1 to C 20 ) When two or more hydrocarbyls are present, they may be the same or different.

[0096] As a combination of neutral Lewis acid activators (cocatalysts), tri((C1-C4) alkyl)aluminum and halogenated tri((C6-C 18)aryl)boron compounds, particularly tris(pentafluorophenyl)borane. Other embodiments include such neutral Lewis acid mixtures in combination with polymeric or oligomeric alumoxanes, and combinations of a single neutral Lewis acid, particularly tris(pentafluorophenyl)borane, with polymeric or oligomeric alumoxanes.

[0097] A catalyst system comprising the metal-ligand complex of formula (I) may be activated to form an active catalyst composition by combining one or more cocatalysts, such as cation-forming cocatalysts, strong Lewis acids, or combinations thereof. Suitable activating cocatalysts include polymeric or oligomeric aluminoxanes, particularly methylaluminoxane, as well as inert, compatible, non-coordinating, ion-forming compounds. Examples of suitable cocatalysts include modified methyl aluminoxane (MMAO), bis(hydrogenated tallow alkyl)methyl, tetrakis(pentafluorophenyl)borate (1 - ) amines, and combinations thereof.

[0098] In some embodiments, one or more of the aforementioned activating cocatalysts are used in combination with each other. Particularly preferred combinations are mixtures of tri((C1-C4)hydrocarbyl)aluminum, tri((C1-C4)hydrocarbyl)borane, or ammonium borate with an oligomeric or polymeric alumoxane compound. The ratio of the total number of moles of the one or more metal-ligand complexes of formula (I) to the total number of moles of the one or more activating cocatalysts is 1:10,000 to 100:1. In some embodiments, the ratio is at least 1:5000, in some other embodiments at least 1:1000, and not more than 10:1, and in some other embodiments not more than 1:1. When an alumoxane is used alone as an activating cocatalyst, preferably the number of moles of aluminum used is at least 10 times the number of moles of the metal-ligand complexes of formula (I). For example, when tris(pentafluorophenyl)borane may be used alone as the activating cocatalyst, in some other embodiments, the number of moles of tris(pentafluorophenyl)borane used relative to the total number of moles of one or more metal-ligand complexes of formula (I) is 0.5:1 to 10:1, 1:1 to 6:1, or 1:1 to 5:1. The remaining activating cocatalyst is generally used in a molar amount approximately equal to the total molar amount of one or more metal-ligand complexes of formula (I).

[0099] film

[0100] In some embodiments, the disclosed embodiments relate to a film formed from any of the disclosed polyethylene compositions described herein. In some embodiments, the film may be a blown film or a cast film. In embodiments, the film may be an extrusion coated film. In embodiments, the film may be a blown machine direction oriented film or a cast film tenter frame oriented film. In some embodiments, the film may be a monolayer film. In some embodiments, the film may be a multilayer film. In some embodiments, the film may be a multilayer film. In some embodiments of a multilayer film comprising the disclosed polyethylene composition, the multilayer film may include the disclosed polyethylene-based composition in a surface layer and / or an inner layer. In embodiments, the disclosed polyethylene composition may be in a sealant layer of a multilayer film, where the polyethylene composition described herein is applied to at least one surface of the substrate layer to form a sealant layer associated with at least one surface of the substrate layer. The sealant layer may be applied to the substrate layer of a blown or cast film, for example, by a coextrusion process. In embodiments, the sealant layer may be applied directly to the substrate layer as an extrusion coating. The sealant layer may provide a heat sealable surface. As used herein, a heat-sealable surface is a surface that may allow a surface of a film to be heat sealed to another surface of the same film or to the surface of another film or substrate.

[0101] In one or more embodiments, the polyethylene compositions of the present disclosure may be blended with other polymers, such as other polyethylenes, or even other non-polyethylene polymers. For example, the polyethylene compositions of the present disclosure may be blended with conventional polyethylene compositions known to those of skill in the art, such as, but not limited to, LDPE, LLDPE, and / or HDPE.

[0102] The amount of polyethylene composition used in the films of the present embodiments can depend on several factors, including, for example, whether the film is a monolayer or multilayer film, the other layers in the film if it is a multilayer film, the end use of the film, etc.

[0103] The films of the present invention may have a variety of thicknesses. The thickness of the film may depend on several factors, including, for example, whether the film is a monolayer film or a multilayer film, the other layers of the film if it is a multilayer film, the desired properties of the film, the end use of the film, the equipment available to manufacture the film, etc. In some embodiments, the films of the present disclosure have a thickness of up to 10 mils. For example, the films may have a thickness of a lower limit of 0.25 mils, 0.5 mils, 0.7 mils, 1.0 mils, 1.75 mils, or 2.0 mils to an upper limit of 4.0 mils, 6.0 mils, 8.0 mils, or 10 mils. In embodiments, the film may have a thickness of 0.25 mils to 2.0 mils, 0.25 mils to 1.75 mils, 0.25 mils to 1.0 mils, 0.25 mils to 0.7 mils, 0.25 mils to 0.5 mils, 0.5 mils to 2.0 mils, 0.5 mils to 1.75 mils, 0.5 mils to 1.0 mils, 0.5 mils to 0.7 mils, 0.7 mils to 2.0 mils, 0.7 mils to 1.75 mils, 0.7 mils to 1.0 mils, 1.0 mils to 2.0 mils, 1.0 mils to 1.75 mils, 1.75 mils to 2.0 mils, or any combination.

[0104] In embodiments where the film comprises a multilayer film, the number of layers of the film can depend on several factors including, for example, the desired properties of the film, the desired thickness of the film, the content of other layers in the film, the end use of the film, the equipment available to manufacture the film, etc. Multilayer blown films can include up to 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11 layers in various embodiments.

[0105] The polyethylene composition may be used in two or more layers of the film in some embodiments. Other layers in the multilayer film of the present disclosure may include polymers selected from the following in various embodiments: the polyethylene composition of the present disclosure, LLDPE, VLDPE (very low density polyethylene), MDPE, LDPE, HDPE, HMWHDPE (high molecular weight HDPE), propylene-based polymers, polyolefin plastomers (POP), polyolefin elastomers (POE), olefin block copolymers (OBC), ethylene vinyl acetate, ethylene acrylic acid, ethylene methacrylic acid, ethylene methyl acrylate, ethylene ethyl acrylate, ethylene butyl acrylate, isobutylene, maleic anhydride grafted polyolefins, ionomers of any of the foregoing, or combinations thereof. In some embodiments, the multilayer film of the present disclosure may include one or more tie layers known to those skilled in the art.

[0106] In additional embodiments of the polyolefin films described herein, other layers may be adhered to the polyethylene film (possibly in addition to the barrier layer), for example, by a tie layer. Tie layers may be used to adhere layers of different materials. For example, a barrier layer comprising ethylene vinyl alcohol (EVOH) may be adhered to a polyethylene material by a tie layer (i.e., a tie layer comprising maleic anhydride grafted polyethylene). For example, the polyolefin film may further comprise other layers typically included in a multi-layer structure depending on the application, including, for example, other barrier layers, structural or strength layers, sealant layers, other tie layers, other polyethylene layers, polypropylene layers, etc. In additional embodiments, a printing layer may be included, which may be an ink layer applied to the film to show product details and other packaging information in various colors.

[0107] It should be understood that any of the foregoing layers may further comprise one or more additives as known to those skilled in the art, such as, for example, antioxidants, UV stabilizers, heat stabilizers, slip agents, antiblocking agents, pigments or colorants, processing aids, crosslinking catalysts, flame retardants, fillers, and blowing agents. In some embodiments, the polyethylene composition comprises up to 5 weight percent of such additional additives. All individual values ​​and subranges from 0 to 5 weight percent are included and disclosed herein. For example, the total amount of additives in the polymer blend can be from a lower limit of 0, 0.5, 1, 1.5, 2, or 2.5 weight percent to an upper limit of 1.5, 2, 2.5, 3, 3.5, 4, 4.5, or 5 weight percent. In embodiments, the total amount of additives in the polymer blend is from 0 wt% to 5 wt%, 0 wt% to 4.5 wt%, 0 wt% to 4 wt%, 0 wt% to 3.5 wt%, 0 wt% to 3 wt%, 0 wt% to 2.5 wt%, 0 wt% to 2 wt%, 0 wt% to 1.5 wt%, 0 wt% to 1 wt%, 0 wt% to 0.5 wt%, 0.5 wt% to 5 wt%, 0.5 wt% to 4.5 wt%, 0.5 wt% to 4 wt%, 0. 5wt%~3.5wt%, 0.5wt%~3wt%, 0.5wt%~2.5wt%, 0.5wt%~2wt%, 0.5wt%~1.5wt%, 0.5wt%~1wt%, 1wt%~5wt%, 1wt Amount%~4.5% by weight, 1%~4% by weight, 1%~3.5% by weight, 1%~3% by weight, 1%~2.5% by weight, 1%~2% by weight, 1%~1.5% by weight, 1.5%~5% by weight, 1.5wt%~4.5wt%, 1.5wt%~4wt%, 1.5wt%~3.5wt%, 1.5wt%~3wt%, 1.5wt%~2.5wt%, 1.5wt%~2wt%, 2wt%~5wt% , 2% to 4.5% by weight, 2% to 4% by weight, 2% to 3.5% by weight, 2% to 3% by weight, 2% to 2.5% by weight, 2.5% to 5% by weight, 2.5% to 4.5% by weight, 2.5% by weight % to 4% by weight, 2.5% to 3.5% by weight, 2.5% to 3% by weight, 3% to 5% by weight, 3% to 4.5% by weight, 3% to 4% by weight, 3% to 3.5% by weight, 3.5% to 5% by weight, 3.5% to 4.5% by weight, 3.5% to 4% by weight, 4% to 5% by weight, 4% to 4.5% by weight, or 4.5% to 5% by weight, or any combination of these ranges.

[0108] By being a polyethylene composition, the polyethylene composition of the present disclosure may be incorporated into multilayer films and articles that are primarily, if not substantially or entirely, composed of polyolefins, or more preferably polyethylene, to provide films and articles that are more easily recyclable, according to some embodiments. The polyethylene-based composition of the present disclosure is particularly advantageous for proving films in which the film is primarily formed from polyethylene. For example, monolayer or multilayer films in which the film primarily comprises polyethylene may have an improved recyclability profile in addition to other advantages that the use of such polymers may provide. In some embodiments, the film comprises 90 weight percent or more of polyethylene, based on the total weight of the film. In other embodiments, the film comprises 91 weight percent or more, 92 weight percent or more, 93 weight percent or more, 94 weight percent or more, 95 weight percent or more, 96 weight percent or more, 97 weight percent or more, 98 weight percent or more, or 99 weight percent or more of polyethylene, based on the total weight of the film.

[0109] In some embodiments, a film comprising a layer formed from the polyethylene-based composition of the present disclosure can be laminated to another film substrate. The substrate can include films comprising polyester, nylon, polypropylene, polyethylene, and combinations. For preferred recyclable substrates, biaxially oriented polyethylene (BOPE) substrates, machine direction oriented polyethylene (MDO) substrates, or coextruded polyethylene films can be included in the laminate structure.

[0110] Films of the present disclosure, in some embodiments, can be corona treated and / or printed (eg, reverse printed or front printed) using techniques known to those of skill in the art.

[0111] In some embodiments, films of the present disclosure may be uniaxially (eg, machine direction) or biaxially oriented using techniques known to those of skill in the art.

[0112] In embodiments, a film comprising the polyethylene composition of the present disclosure prepared according to the methods described below may be sealed according to ASTM F88 and have a heat seal initiation temperature of 40°C to 80°C, for example, peeled at a speed of 10 inches / minute after a dwell time of 0.5 seconds, a seal bar pressure of 40 psi, and at least 24 hours. The maximum load measured during peeling may be determined at multiple seal temperatures and the temperature at which an average maximum load of 2 pounds is achieved, which is defined as the "heat seal initiation temperature." For example, in embodiments, a multilayer film comprising the polyethylene composition of the present disclosure prepared according to the methods described below may have a heat seal initiation temperature of 40°C to 80°C, 40°C to 70°C, 40°C to 60°C, 40°C to 50°C, 50°C to 80°C, 50°C to 70°C, 50°C to 60°C, 60°C to 80°C, 60°C to 70°C, 70°C to 80°C, or any combination. Similar methods may be utilized to observe the heat seal initiation temperatures of monolayer and other multilayer films. In embodiments, the monolayer and other multilayer films may have lower heat seal initiation temperatures than comparative films that do not utilize the polyethylene compositions described herein. The polyethylene compositions of the present disclosure may provide films with relatively high density and relatively high heat seal initiation temperatures.

[0113] In embodiments, a film comprising the polyethylene composition of the present disclosure prepared according to the methods described below creates, for example, a 0.5 inch deep and 1 inch wide seal and has a strength of 0.275 N / mm when measured according to ASTM F1921 (Method B). 2For example, after a dwell time of 0.18 seconds, the seal area may be peeled at a speed of 200 mm / sec. The maximum load measured during peeling may be determined at multiple seal temperatures and the temperature at which an average maximum load of 4N is achieved, which is defined as the tack initiation temperature. In an embodiment, a film comprising the polyethylene composition of the present disclosure prepared according to the method described below may have a hot tack initiation temperature of 50°C to 90°C, 50°C to 80°C, 50°C to 70°C, 50°C to 60°C, 60°C to 90°C, 60°C to 80°C, 60°C to 70°C, 70°C to 90°C, 70°C to 80°C, 80°C to 90°C, or any combination. Similar methods may be utilized to observe the hot tack initiation temperatures of monolayer and other multilayer films. In embodiments, monolayer and other multilayer films may have a lower hot tack initiation temperature than comparative films that do not utilize the polyethylene compositions described herein. The polyethylene compositions of the present disclosure may provide films with relatively high density and relatively low hot tack initiation temperatures.

[0114] In embodiments, films comprising the polyethylene compositions of the present disclosure may have a blocking force of less than 40 mN / inch or less than 35 mN / inch when measured according to the methods described below. Similar methods may be used to observe the blocking force of monolayer and other multilayer films. Monolayer and other multilayer film embodiments may have a blocking force comparable to or lower than comparative films that do not utilize the polyethylene compositions described herein.

[0115] Goods

[0116]

[0013] Embodiments of the present disclosure also relate to articles such as packaging formed from or incorporating (i.e., via a film that incorporates) the polyethylene compositions of the present disclosure. Such packaging may be formed from any of the polyethylene-based compositions of the present disclosure (i.e., via a film that incorporates the polyethylene-based composition of the present disclosure) described herein. Such packaging formed from any of the polyethylene compositions of the present disclosure may be sealable by various sealing methods known in the art, such as heat sealing methods.

[0117] Examples of such articles can include flexible packaging, pouches, stand-alone pouches, and pre-formed packages or pouches. In some embodiments, the multilayer films or laminates of the present disclosure can be used in food packages. Examples of food products that can be included in such packages include meat, cheese, cereal, nuts, snacks, juice, sauce, and others. Such packages can be formed using techniques known to those skilled in the art based on the teachings herein and based on the particular application of the package (e.g., type of food, amount of food, etc.).

[0118] A low heat seal initiation temperature, such as that provided by the polyethylene composition of the present invention, may be particularly desirable for automated packaging systems where the packaged article is filled into the package as it is being made. A lower heat seal initiation temperature may be advantageous in increasing packaging productivity by minimizing the time and energy required to heat and cool the sealant. In the case of recyclable polyethylene packaging with an inner sealant layer that seals at a temperature significantly lower than that of the outer polyethylene layer, a wider temperature range may be allowed for making the heat sealed package, which may often be referred to as the package heat seal window. Some examples of such automated packaging equipment are referred to as vertical form fill and seal (VFFS) machines or horizontal form fill and seal (HFFS) machines.

[0119] Test Method

[0120] Unless otherwise indicated herein, the following analytical methods are used in describing the embodiments of the present disclosure.

[0121] Melt Index

[0122] The melt index I2 (or I2) and I 10 (or I10) were measured according to ASTM D-1238 (Method B) at 190° C. and loads of 2.16 kg and 10 kg, respectively, and the values ​​are reported in g / 10 min.

[0123] density

[0124] Samples for density measurements were prepared according to ASTM D4703. Measurements were performed according to ASTM D792, Method B, within 1 hour of sample pressing.

[0125] Creep Zero Shear Viscosity Measurement Method

[0126] Zero shear viscosity is obtained via creep testing performed on an AR-G2 stress-controlled rheometer (TA Instruments, New Castle, Del.) using 25 mm diameter parallel plates at 190° C. The rheometer oven is set to the test temperature for at least 30 minutes before zeroing the fixture. At the test temperature, a compression molded sample disk is inserted between the plates and allowed to equilibrate for 5 minutes. The upper plate is then lowered 50 μm above the desired test gap (1.5 μm). Any excess material is trimmed away and the upper plate is lowered to the desired gap. Measurements are performed under a nitrogen purge with a flow rate of 5 L / min. The initial creep time is set to 2 hours.

[0127] To ensure that the steady-state shear rate is low enough in the Newtonian region, all of the samples are subjected to a constant low shear stress of 20 Pa. The resulting steady-state shear rate is 10 for the samples in this study. -3 ~10 -4 s -1 The steady state is determined by taking a linear regression on all the data in the last 10% time window of a plot of log(J(t)) versus log(t), where J(t) is the creep compliance and t is the creep time. If the slope of the linear regression is greater than 0.97, the steady state is considered to have been reached and the creep test is then stopped. In this study, in all cases, the slope meets the criterion within 2 hours. The steady state shear rate is determined from the slope of the linear regression of all the data points in the last 10% time window of a plot of ε versus t, where ε is the strain. The zero shear viscosity is determined from the ratio of the applied stress to the steady state shear rate.

[0128] To determine if the specimen has degraded during the creep test, perform small amplitude oscillatory shear tests before and after the creep test on the same specimen at 0.1 to 100 rad / s. Compare the complex viscosity values ​​of the two tests. If the difference in viscosity value at 0.1 rad / s is greater than 5%, consider the specimen to have degraded during the creep test and discard the results.

[0129] Gel Permeation Chromatography (GPC)

[0130] The chromatography system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment was set at 160° Celsius and the column compartment was set at 150° Celsius. The columns used were four Agilent "Mixed A" 30 cm 20 micron linear mixed bed columns and a 20 um precolumn. The chromatography solvent used was 1,2,4-trichlorobenzene containing 200 ppm butylated hydroxytoluene (BHT). The solvent source was nitrogen sparged. The injection volume used was 200 microliters and the flow rate was 1.0 milliliters / min.

[0131] Calibration of the GPC column set was performed with 21 narrow molecular weight distribution polystyrene standards with molecular weights ranging from 580 to 8,400,000, arranged in six "cocktail" mixtures with at least 10-fold spacing between individual molecular weights. Standards were purchased from Agilent Technologies. Polystyrene standards were prepared at 0.025 grams in 50 milliliters of solvent for molecular weights of 1,000,000 and above, and 0.05 grams in 50 milliliters of solvent for molecular weights below 1,000,000. The polystyrene standards were dissolved at 80 degrees Celsius for 30 minutes with gentle agitation. The peak molecular weights of the polystyrene standards were converted to polyethylene molecular weights using Equation 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)).

number

[0132] A fifth order polynomial was used to fit each of the polyethylene equivalent calibration points, with a small adjustment to A (approximately 0.375 to 0.445) to correct for column resolution and band broadening effects for a linear homopolymer polyethylene standard obtained at 120,000 Mw.

[0133] Total plate counts of the GPC column set were performed using decane (prepared at 0.04 g in 50 milliliters of TCB and dissolved for 20 minutes with gentle agitation). Plate counts (Equation 2) and symmetry (Equation 3) were measured with a 200 microliter injection according to the following equations:

number

number

[0134] Samples were prepared in a semi-automated fashion using the PolymerChar "Instrument Control" software to target sample weight of 2 mg / ml and add solvent (containing 200 ppm BHT) via the PolymerChar high temperature autosampler to a pre-nitrogen sparged septa-capped vial. Samples were dissolved at 160 degrees Celsius under "slow" shaking for 2 hours.

[0135] Mn (GPC) , Mw (GPC), and Mz (GPC) The calculation was based on GPC results using PolymerChar GPCOne™ software, baseline-subtracted IR chromatograms at each equally spaced data collection point (i), and the polyethylene equivalent molecular weights obtained from a narrow standard calibration curve at point (i) in Equation 1, according to Equations 4-6, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR chromatograph.

number

number

[0136] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (apparent)) of each sample by RV matching the respective decane peak in the sample (RV (FM sample)) with that of the decane peak in the narrow standard calibration (RV (FM calibrated)). Any change in time of the decane marker peak is then assumed to be related to a linear shift in flow rate (flow rate (effective)) throughout the run. To facilitate the highest accuracy of the RV measurement of the flow rate marker peak, a least squares fitting routine is used to fit the peaks of the flow rate marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation is then used to solve for the true peak position. After calibrating the system based on the flow rate marker peak, the effective flow rate (relative to the narrow standard calibration) is calculated as in Equation 7. Processing of the flow rate marker peaks was performed via PolymerChar GPCOne™ software. An acceptable flow correction is that the effective flow is within + / - 0.5% of the apparent flow.

number

[0137] Improved Method for Comonomer Content Distribution (iCCD) Analysis

[0138] An improved comonomer content analysis method (iCCD) was developed in 2015 (Cong and Parrott et al., WO 2017040127(A1)). iCCD testing was performed using a Crystallization Elution Fractionation (CEF) instrument (PolymerChar, Spain) equipped with an IR-5 detector (PolymerChar, Spain) and a two-angle light scattering detector model 2040 (Precision Detectors, now Agilent Technologies). A guard column of 20-27 micron glass (MoSCi Corporation, USA) packed in 5 or 10 cm (length) x ¼ inch (ID) stainless steel was placed immediately before the IR-5 detector in the detector oven. Orthodichlorobenzene (ODCB, 99% anhydrous grade or technical grade) was used. Silica gel 40 (particle size 0.2-0.5 mm, catalog number 10181-3) was obtained from EMD Chemicals (can be used to dry the ODCB solvent prior). The CEF instrument is equipped with an autosampler with N2 purge capability. ODCB is sparged with dry nitrogen (N2) for 1 hour prior to use. Sample preparation is performed using the autosampler at 4 mg / ml (unless otherwise specified) with shaking at 160 °C for 1 hour. Injection volume was 300 μl. The temperature profile for the iCCD was crystallization from 105 °C to 30 °C at 3 °C / min, thermal equilibration at 30 °C for 2 minutes (including setting the soluble fraction elution time to 2 minutes), and elution from 30 °C to 140 °C at 3 °C / min. The flow rate during crystallization is 0.0 ml / min. The flow rate during elution is 0.50 ml / min. Data is collected at 1 data point / sec.

[0139] The iCCD column was packed with gold-coated nickel particles (Bright 7GNM8-NiS, Nippon Chemical Industrial Co.) in a 15 cm (length) x ¼ inch (ID) stainless steel tube. Column packing and conditioning was performed with a slurry method according to references (Cong, R.; Parrott, A.; Hollis, C.; Cheatham, M. WO 2017040127 (A1)). The final pressure using TCB slurry packing was 150 bar.

[0140] Column temperature calibration was performed using the reference material linear homopolymer polyethylene in ODCB (comonomer content zero, melt index (I2) 1.0, polydispersity M w / M n The iCCD temperature calibration was performed using a mixture of ethylenediaminetetraacetate (1.0 mg / ml) and eicosane (2 mg / ml), which has a peak elution temperature of approximately 2.6 for conventional gel permeation chromatography. The iCCD temperature calibration consisted of four steps: (1) calculating the delay volume, defined as the temperature offset between the measured peak elution temperatures of eicosane minus 30.00°C; (2) subtracting the temperature offset of the elution temperature from the iCCD raw temperature data, note that this temperature offset is a function of the experimental conditions such as elution temperature, elution flow rate, etc.; and (3) creating a linear calibration line that converts the elution temperatures over the range of 30.00°C to 140.00°C, such that the linear homopolymer polyethylene reference material has a peak temperature at 101.0°C and eicosane has a peak temperature of 30.0°C. (4) For the soluble fraction measured isothermally at 30°C, elution temperatures below 30.0°C are linearly extrapolated by using an elution heating rate of 3°C / min according to reference (Cerk and Cong et al., U.S. Pat. No. 9,688,795).

[0141] Comonomer content versus iCCD elution temperature was constructed using 12 reference materials (ethylene homopolymers and ethylene-octene random copolymers made with a single-site metallocene catalyst, with ethylene equivalent weight average molecular weights ranging from 35,000 to 128,000). All of these reference materials were analyzed in the same manner as previously specified at 4 mg / mL. The reported elution peak temperatures were linearly fitted to the linear equation y=-6.3515x.+101.00, where y represents the iCCD elution temperature, x represents the octene mole %, and R 2 was 0.978.

[0142] The molecular weights of the polymers and polymer fractions were determined directly from the LS detector (at a 90 degree angle) and the concentration detector (IR-5) according to the Rayleigh-Gans-Debys approximation (Striegel and Yau, "Modern Size Exclusion Liquid Chromatogram", pp. 242 and 263) by assuming a form factor of 1 and all virial coefficients of zero. Set the integration window to integrate all chromatograms with elution temperatures ranging from 23.0 to 120 °C (temperature calibration specified above).

[0143] Calculation of molecular weight (Mw) from iCCD involves four steps:

[0144] (1) Measure the inter-detector offset. The offset is defined as the geometric volume offset between the LS detector and the concentration detector. It is calculated as the difference in elution volume (mL) of the polymer peak between the concentration detector and the LS chromatogram. This is converted to a temperature offset by using the elution heat rate and elution flow rate. A linear high-density polyethylene (comonomer content zero, melt index (I2) 1.0, polydispersity M w / M nConventional gel permeation chromatography uses about 2.6). The same experimental conditions as the regular iCCD method described above are used, except for the following parameters: crystallization from 140°C to 137°C at 10°C / min, 1 minute thermal equilibration as soluble fraction elution time at 137°C, 7 minutes soluble fraction (SF) time, elution from 137°C to 142°C at 3°C / min. The flow rate during crystallization is 0.0 ml / min. The flow rate during elution is 0.80 ml / min. The sample concentration is 1.0 mg / ml.

[0145] (2) Shift each LS data point in the LS chromatogram to correct for inter-detector offset before integration.

[0146] (3) The baseline-subtracted LS and concentration chromatograms are integrated over the elution temperature range of step (1). The MW detector constant is calculated using HDPE samples of known MW in the range of 100,000-140,000 MW and the area ratio of the LS and concentration integrated signals.

[0147] (4) The Mw of the polymer was calculated using the ratio of the integrated light scattering detector (at a 90 degree angle) to the concentration detector and using the MW detector constant.

[0148] The half-width calculation is defined as the temperature difference between the forward and rearward temperatures at half the maximum peak height, where the forward temperature at half the maximum peak is searched forward from 35.0°C and the rearward temperature at half the maximum peak is searched backward from 119.0°C.

[0149] Zero-shear viscosity ratio (ZSVR)

[0150] ZSVR is defined as the ratio of the zero-shear viscosity (ZSV) of a branched polyethylene material to the ZSV of a linear polyethylene material at equivalent weight average molecular weight (Mw-gpc) according to Equations 8 and 9 below:

number

[0151] ZSV values ​​were obtained from creep tests at 190°C by the method described above. Mw-gpc values ​​were determined by the conventional GPC method (Equation 5 in the description of the conventional GPC method). A correlation between the ZSV of a linear polyethylene and its Mw-gpc was established based on a series of linear polyethylene reference materials. A description of the ZSV-Mw relationship can be found in the ANTEC Abstract: Karjala, Teresa P., Sammler, Robert L., Mangnus, Marc A., Hazlitt, Lonnie G., Johnson, Mark S., Hagen, Charles M. Jr., Huang, Joe WL, Reichek, Kenneth N., "Detection of low levels of long-chain branching in polyolefins", Annual Technical Conference-Society of Plastics Engineers (2008), 66th 887-891.

[0152] Blocking Force

[0153] Blocking force measurements are sensitive to the thermal history of the film samples. The films were produced on a Labtech 5-layer blown film line (as further described in Example 5 below). The blown film was folded at the nip after the bubble and was not separated and slit into two webs. The samples tested for blocking force were made, stored, and tested at a temperature of 23±2° C. A 6 inch by 1 inch strip was first punched out of the folded bubble of film with the longer dimension along the machine direction. Approximately 1 inch length of the two layers was separated by hand at one end. The separated layers were clamped in the grips of an Instron frame (initial grip separation=1.5 inches) and pulled apart (180° peel) at a rate of 1 inch / min. The test was continued until an additional 4 inches of layers were separated. Force-displacement curves were recorded during the test. The force increased rapidly at first and then plateaued. The plateau force is a measure of the blocking force. When the layers are separated, some "spikes" of force may be observed. The spikes may be due to improper cutting of the film, which leaves random points along the length of the specimen "sticked" together. To avoid misidentification of the blocking force due to these spikes, the most frequent value of the force in the plateau region (mode) was taken as a measure of blocking, instead of the average (Mean). At least five specimens were tested from each folded bubble. Results were reported as the mean ± standard deviation of the blocking force measured from all samples.

[0154] Hot tack start temperature

[0155] Hot tack refers to the strength of the heat seal formed between films after the seal is made and before it is cooled to room temperature. Hot tack testing can be used to determine the seal strength and appropriate sealing parameters of the heat sealing process. Hot tack initiation temperature was measured according to ASTM F1921 (Method B).

[0156] Heat seal start temperature

[0157] The heat seal test can be used to determine suitable sealing parameters of the film, such as sealing temperature, dwell time, and pressure. Heat seal initiation temperature was measured according to ASTM F-88 (Technique A).

[0158] Dynamic Shear Rheology

[0159] The samples were compression molded at 190°C and 25,000 pounds pressure for 6.5 minutes in air, after which the plaques were allowed to cool on the lab bench. The thickness of the plaques was approximately 3 mm. Constant temperature frequency sweep measurements were performed on an ARES strain-controlled parallel plate rheometer (TA Instruments) equipped with 25 mm parallel plates under a nitrogen purge. For each measurement, the rheometer was allowed to thermally equilibrate for at least 30 minutes before the gap was zeroed. The sample was placed on the plates and melted at 190°C for 5 minutes. The plates were then closed to 2 mm, the sample was trimmed, and the test was then started. The method incorporated an additional 5 minute delay to allow for temperature equilibration. The experiments were performed at 190°C over a frequency range of 0.1 to 100 rad / sec, with 5 points per decade interval. The strain amplitude was constant at 10%. The stress response was analyzed in terms of amplitude and phase, from which the storage modulus (G'), loss modulus (G''), complex modulus (G * ), dynamic complex viscosity (η * ), and tan(δ) or tan delta were calculated. EXAMPLES

[0160] Example 1: Preparation of polyethylene compositions 1 to 3

[0161] Polyethylene compositions 1-3 described according to one or more embodiments of the detailed description were prepared by the methods and utilizing the catalysts and reactors described below.

[0162] All raw materials (monomers and comonomers) and process solvents (high purity narrow boiling range isoparaffinic solvent, Isopar-E) were purified with molecular sieves prior to introduction into the reaction environment. Hydrogen was supplied under pressure as a high purity grade with no further purification. The reactor monomer feed stream was pressurized above the reaction pressure via a mechanical compressor. Solvent and comonomer feeds were pressurized to pressures above the reaction pressure via pumps. Individual catalyst components were manually batch diluted with purified solvent and pressurized to the reaction pressures listed above. All reaction feed streams were measured with mass flow meters and independently controlled with computerized automated valve control systems.

[0163] As shown in FIG. 2, a two-reactor system was used in a series configuration. Each continuous solution polymerization reactor utilized a liquid-filled, non-adiabatic, isothermal, circulating, loop reactor that mimicked a continuously stirred tank reactor (CSTR) with heat removal. Independent control of all fresh solvent, monomer, comonomer, hydrogen, and catalyst component feeds was possible. All fresh feed streams to each reactor (solvent, monomer, comonomer, and hydrogen) were temperature controlled to maintain a single solution phase by passing the feed streams through heat exchangers. The total fresh feed to each polymerization reactor was injected into the reactor at two locations, with reactor volumes approximately equal between each injection location. Fresh feed was controlled so that each injector received half of the total fresh feed mass flow rate. Catalyst components were injected into the polymerization reactor through injection stringers. Catalyst feed was computer controlled to maintain the monomer conversion of each reactor at a specific target. Cocatalyst components were fed to the primary catalyst components based on a calculated specific molar ratio. Immediately after each reactor feed injection point, the feed stream was mixed with the contents of the circulation polymerization reactor using a static mixing element. The contents of each reactor were continuously circulated through a heat exchanger that removed most of the heat of reaction and a coolant side that maintained an isothermal reaction environment at a specific temperature. Circulation around each reactor loop was provided by a pump.

[0164] The effluent from the first polymerization reactor (containing solvent, monomer, comonomer, hydrogen, catalyst components, and polymer) exited the first reactor loop and was added to the second reactor loop.

[0165] The second reactor effluent entered a zone where it was deactivated by addition and reaction with a suitable reagent (water).At this same reactor outlet location, other additives were added for polymer stabilization (typical antioxidants suitable for stabilization during extrusion and film fabrication, such as octadecyl 3,5-di-Tert-butyl-4-hydroxyhydrocinnamate, tetrakis(methylene(3,5-di-Tert-butyl-4-hydroxyhydrocinnamate))methane, and tris(2,4-di-Tert-butyl-phenyl)phosphite).

[0166] Following catalyst deactivation and additive addition, the reactor effluent entered a devolatilization system where polymer was removed from the non-polymer stream. The isolated polymer melt was pelletized and collected. The non-polymer stream passed through various equipment that separated most of the ethylene removed from the system. Most of the solvent and unreacted comonomer were recycled to the reactor after passing through a purification system. Small amounts of solvent and comonomer were purged from the process.

[0167] Reactor stream feed data flows corresponding to the values ​​in Table 1. The data is presented so that the complexity of the solvent recycle system is taken into account and the reaction system can be more easily treated as a once-through flow diagram. Table 2 shows the catalysts referenced in Table 1. [Table 1] [Table 2]

[0168] Example 2: Comparative Compositions A to G

[0169] Table 3 identifies commercially available polyethylene compositions for Comparative Polyethylene Compositions A-G. [Table 3]

[0170] Example 3: Analysis of Polyethylene Compositions 1 to 3 of Example 1 and Comparative Polyethylene Compositions A to G of Example 2

[0171] Polyethylene compositions 1-3 of Example 1 and comparative polyethylene compositions A-G of Example 2 were analyzed by iCCD. Data generated from iCCD testing of all samples (Polyethylene Compositions 1-3 of Example 1 and Comparative Polyethylene Compositions A-G) are provided in Tables 4A and 4B. Specifically, Table 4A includes an analysis of the iCCD data at temperature increments of 5° C. [Table 4]

[0172] Table 4B further depicts the iCCD data, including the areas of each polyethylene fraction (25°C to 35°C, 35°C to 70°C, 70°C to 85°C, and 85°C to 120°C). [Table 5]

[0173] As shown in Tables 4A and 4B, samples of polyethylene compositions 1-3 exhibited a maximum percentage in the range of 85° C. to 120° C. and a minimum percentage in the range of 70° C. to 85° C. In addition, none of the samples of comparative polyethylene compositions A, B, C, F, or G exhibited a polyethylene fraction between 70° C. and 85° C. that constituted less than 10% of the total area of ​​the elution profile. In addition, comparative polyethylene compositions D and E failed to exhibit a polyethylene fraction between 85° C. and 120° C. that constituted at least 20% of the total area of ​​the elution profile.

[0174] Table 5 provides additional data for each sample of Comparative Polyethylene Compositions A-G and Polyethylene Compositions 1-3, including overall density, melt index, ZSVR, and ratio of first fraction molecular weight to overall molecular weight. These properties were measured according to the test methods described herein. [Table 6]

[0175] As previously described in this disclosure, tan delta (tan δ) is a measure of how close a material is to a perfect elastic solid (d=0°, tan delta=0) or how close a material is to a perfect Newtonian liquid (d=90°, tan delta=infinity). Thus, lower values ​​of tan d reflect higher elasticity. Tan d is a function of LCB and MWD at the same overall molecular weight. Higher tan d values ​​indicate lower LCB. [Table 7]

[0176] As shown in Table 6, polyethylene compositions 1 and 2 had tan δ of 27.3 and 22.3, respectively. Polyethylene composition 3 had a tan δ of 80.9. In comparison, comparative polyethylene composition A had a tan δ of 50.3, and comparative polyethylene compositions B to G each had a relatively low tan δ value (5.9, 4.9, 6.3, 6.04, 10.4, and 10.4, respectively).

[0177] Example 4: Analysis of heat seal initiation temperature and hot tack initiation temperature

[0178] In Example 4, films comprising the polyethylene compositions described herein were analyzed for heat seal initiation temperature and hot tack initiation temperature.

[0179] To analyze these properties, multilayer films were coextruded on an Alpine 7-layer blown film line. The line was equipped with seven 50 mm single screw extruders with 30 L / D and a 250 mm die. Three-layer (skin, core, and sealant) films with a total thickness of 2 mils were produced. The thickness ratio of the skin / core / sealant layers was set at 1 / 3 / 1. The skin layers consisted of an 80 / 20 (by weight) blend of DOWLEX™ 2045G / LDPE 611A, both commercially available from The Dow Chemical Company. The base resin of the core layer consisted of the same blend as the skin layers, but in addition included 500 ppm of 10090 Slip PE MB (erucamide, commercially available from Ampacet Corporation) and 10063 Antiblock PE MB (commercially available from Ampacet Corporation), which were added by dry blending. The polyethylene composition used in the sealant layer was varied as provided in Table 7 below. 750 ppm of 10090 Slip PE MB and 2500 ppm of 10063 Antiblock PE MB were introduced into the sealant layer via dry blending. The die gap was set at 78.7 mils, blow-up ratio at 2.5, melt temperature at 440°F-470°F, output rate at 350 lbs / hr, and frost line height at approximately 37 inches. The multilayer film bubble was slit in-line and separated into two rolls. [Table 8]

[0180] Each of Films 1-3 and Comparative Films A-E was then laminated onto 0.48 mil thick polyethylene terephthalate (PET) using a Nordmeccanica Super Combi 3000 laminator with ADCOTE™ 577 / CR87-124 solvent-based adhesive, the ADCOTE™ 577 and CR87-124 components being mixed in a 100:7 weight ratio. Prior to application of the solvent-based adhesive, the skin side of each of Films 1-3 and Comparative Films A-E was corona irradiated at 1 kW. The adhesive was applied via a gravure roll using a 150 channel quad with 11.5 bcm producing a coating weight of 1.75 lb / rm, followed by nipping at 180°F. The films were allowed to cure at 25°C and 40% relative humidity for at least 5-7 days for full chemical cure to produce Laminated Films 1-3 and Comparative Laminated Films A-E.

[0181] Hot tack measurements were performed on each of the laminated films 1-3 and the comparative laminated films A-E using an Enepay commercial tester according to ASTM F-1921 (Method B). Prior to testing, the samples were conditioned for a minimum of 40 hours at 23°C and 50% RH according to ASTM D-618 (Procedure A).

[0182] Sheets measuring 8.5 inches by 14 inches were cut from the film with the longest dimension in the machine direction. Strips 1 inch wide and 14 inches long were cut from the sheets. Tests were run on these samples at a range of temperatures and results reported as maximum load as a function of temperature. These temperature steps were 5°C or 10°C and were repeated six times at each temperature. The parameters used in the test were 25.4 mm (1.0 inch) specimen width, 0.275 N / mm 2The sealing pressure was 0.02 mm, sealing dwell time was 0.5 seconds, delay time was 0.18 seconds, peel speed was 200 mm / sec, and seal depth was 0.5 inches. A hot tack curve was generated by linear interpolation of the average maximum load measured at each temperature. The lowest temperature at which an average maximum load of 4 N was achieved (defined as the hot tack initiation temperature) was determined from this curve and is reported in Table 8.

[0183] Heat seal measurements were performed on each of the Laminated Films 1-3 and Comparative Laminated Films AE using a commercially available tensile tester according to ASTM F-88 (Technique A).

[0184] Prior to cutting, the film was conditioned for a minimum of 40 hours at 23° C. (±2° C.) and 50% (±10%) RH according to ASTM D-618 (Procedure A). Sheets were then cut from the film to approximately 11 inches long and approximately 8.5 inches wide in the machine direction. The sheets were subjected to a tensile strength of 0.275 N / mm 2 The sheets were heat sealed along the machine direction on a Kopp Heat sealer at a range of temperatures under the following conditions: sealing pressure of 1.0 s, sealing dwell time of 1.0 s, and seal depth of 5 mm. The sealed sheets were conditioned for a minimum of 3 hours at 23°C (±2°C) and 50% RH (±10%) before cutting into 1 inch wide strips. The samples were conditioned for a minimum of 24 hours after sealing at 23°C (±2°C) and 50% RH (±10%) prior to testing. For testing, the strips were loaded into the grips of a tensile tester with an initial separation of 2 inches and pulled at a grip separation speed of 10 inches / min at 23°C (±2°C) and 50% RH (±10%). The strips were tested unsupported. Five replicates were performed for each sealing temperature. The maximum load measured during peel was determined at multiple sealing temperatures, and heat seal curves were generated by linear interpolation of the average maximum load measured at each temperature. The temperature at which an average maximum load of 2 pounds was achieved (defined as the heat seal initiation temperature) was determined from this curve and is provided subsequently in Table 8. [Table 9]

[0185] As shown in Table 8, Laminated Films 1 to 3 exhibited the lowest hot tack initiation temperatures and heat seal initiation temperatures among Laminated Films 1 to 3 and Comparative Laminated Films A to E.

[0186] Example 5: Blocking Force Analysis

[0187] In Example 5, blocking force was analyzed for films comprising the polyethylene compositions described herein. Blocking force measurements can be sensitive to the thermal history of the sample. All samples tested for blocking force were fabricated and then stored and tested at a temperature of 23±° C.

[0188] In this example, the multilayer films were coextruded on a LabTech 5-layer blown film line. The line was equipped with two 25mm and three 20mm single screw extruders of 30L / D and a 75mm die. A two-layer (skin and sealant) film with a total thickness of 2 mils was produced. The thickness ratio of the skin / core / sealant layers was set at 4 / 1. The skin layer was composed of an 80 / 20 (by weight) blend of DOWLEX™ 2045G / LDPE 611A. The polyethylene composition used for the sealant layer was varied as provided in Table 9 below. [Table 10]

[0189] The blow-up ratio was set at 3.0, the output rate was 40 lbs / hr, the distance between the nip roll and the die was 81 inches, the nip roll pressure was 0.5 MPa, the extruder exit temperature of the sealant was 230° C., the mandrel and exit die temperatures were 230° C., and no internal bubble cooling was used.

[0190] Approximately 20 feet of the folded bubble was collected by hand. A 6" x 1" strip was then punched from the folded bubble of film with its longer dimension along the machine direction. Two layers approximately 1" long were separated by hand at one end. The separated layers were clamped in the grips of an Instron frame (initial grip separation = 1.5") and pulled apart (180° peel) at a rate of 1" / min. The test continued until an additional 4" of layers were separated. Force-displacement curves were recorded during the test. The force increased rapidly at first and then plateaued. The plateau force is a measure of the blocking force. Several "spikes" in force may be observed when the layers are separated. The spikes may be due to improper cutting of the film, which leaves random points along the length of the specimen that are "sticked" together. To avoid misinterpretation of the blocking force due to these spikes, the most frequent value of the force in the plateau region (mode) was taken as a measure of blocking instead of the average (Mean). At least five specimens were tested from each folded bubble. The results are reported in Table 10 as the mean ± standard deviation of the blocking force measured from all specimens. [Table 11]

[0191] The results in Table 10 show that Sample Films 4 and 5, each comprising an embodiment of the polyethylene composition described herein, exhibit blocking forces comparable to Comparative Film G and lower than Comparative Film H, respectively.

[0192] Example 6:

[0193] In Example 6, the heat seal initiation temperature and hot tack initiation temperature were analyzed for monolayer films comprising the polyethylene compositions described herein.

[0194] To analyze these properties, monolayer films were coextruded on a LabTech 5-layer blown film line. Monolayer film 1 was produced from polyethylene composition 1 of Example 1 above. Monolayer film 2 was produced from polyethylene composition 2 of Example 1 above. Comparative monolayer film D was produced from comparative polyethylene composition D of Example 2 above (AFFINITY™ PL 1880G, Dow Chemical Co.). Comparative monolayer film E was produced from comparative polyethylene composition E of Example 2 above (AFFINITY™ PF 1140G, Dow Chemical Co.). The line was equipped with two 25 mm and three 20 mm single screw extruders with 30 L / D and a 75 mm die. Films with a total thickness of 2 mils were produced. The die gap was set at 78.7 mils, the blow-up ratio at 3.0, the melt temperature at 425°F to 445°F, the output rate at 25 to 30 lbs / hr, and the frost line height at 6 to 7 in. The monolayer film bubble was slit in-line and separated into two rolls.

[0195] Hot tack measurements on the fill were performed using an Enepay commercial tester according to ASTM F-1921 (Method B) for each of the monolayer films 1 and 2 and the comparative monolayer films D and E. Prior to testing, the samples were conditioned for a minimum of 40 hours at 23° C. and 50% RH according to ASTM D-618 (Procedure A).

[0196] Sheets measuring 8.5 inches by 14 inches were cut from the film with the longest dimension in the machine direction. Strips 1 inch wide and 14 inches long were cut from the sheets. Tests were run on these samples at a range of temperatures and results reported as maximum load as a function of temperature. Temperature steps were 5°C or 10°C with six repeats at each temperature. The parameters used in the test were as follows: 25.4 mm (1.0 inch) specimen width, 0.275 N / mm 2The sealing pressure was 0.02 N, sealing dwell time was 0.5 seconds, delay time was 0.18 seconds, peel speed was 200 mm / sec, and seal depth was 0.5 inches. A hot tack curve was generated by linear interpolation of the average maximum load measured at each temperature. The lowest temperature at which an average maximum load of 2 N was achieved (defined as the hot tack initiation temperature) was determined from this curve and is reported in Table 11.

[0197] Heat seal measurements were performed on each of the monolayer films 1 and 2 and the comparative monolayer films D and E using a commercially available tensile tester according to ASTM F-88 (technique A).

[0198] Prior to cutting, the film was conditioned for a minimum of 40 hours at 23° C. (±2° C.) and 50% (±10%) RH according to ASTM D-618 (Procedure A). Sheets were then cut from the film to approximately 11 inches long and approximately 8.5 inches wide in the machine direction. The sheets were subjected to a tensile strength of 0.275 N / mm 2 The strips were heat sealed along the machine direction on a Kopp Heat sealer at a range of temperatures under the following conditions: sealing pressure of 1.0 s, sealing dwell time of 1.0 s, and seal depth of 5 mm. The sealed sheets were conditioned for a minimum of 3 hours at 23°C (±2°C) and 50% RH (±10%) before cutting into 1 inch wide strips. The samples were conditioned for a minimum of 24 hours after sealing at 23°C (±2°C) and 50% RH (±10%) before testing. For testing, the strips were loaded into the grips of a tensile tester with an initial separation of 2 inches and pulled at a grip separation speed of 10 inches / min at 23°C (±2°C) and 50% RH (±10%). The strips were tested unsupported. Five replicates were run for each sealing temperature. The maximum load measured during peel was determined at multiple sealing temperatures, and heat seal curves were generated by linear interpolation of the average maximum load measured at each temperature. The temperature at which an average maximum load of 1 pound was achieved (defined as the heat seal initiation temperature) was determined from this curve and is provided subsequently in Table 11. [Table 12]

[0199] As shown in Table 11, monolayer films 1 and 2 exhibited lower hot tack initiation temperatures and heat seal initiation temperatures than comparative monolayer films D and E.

[0200] It will be apparent that modifications and variations are possible without departing from the scope of the present disclosure, as defined in the appended claims. More specifically, although certain aspects of the present disclosure are identified herein as preferred, exemplary, or particularly advantageous, it is contemplated that the present disclosure is not necessarily limited to those aspects.

[0201] It should be noted that one or more of the claims that follow utilize the term "herein" as a transitional phrase. It should be noted that for purposes of defining the invention, this term is introduced into the claims as an open-ended transitional phrase used to introduce a recitation of a series of features of a structure, and is to be interpreted in a similar manner to the more commonly used open-ended preamble term "comprising."

Claims

1. 1. A polyethylene composition comprising: (a) a first polyethylene fraction comprising at least one peak in a temperature range of 35° C. to 70° C. in an elution profile via an improved comonomer composition distribution (iCCD) analysis method, wherein the area of ​​the first polyethylene fraction is an area in the elution profile from 35° C. to 70° C., and the area of ​​the first polyethylene fraction constitutes 25% to 65% of the total area of ​​the elution profile; (b) a second polyethylene fraction comprising at least one peak in the temperature range of 85°C to 120°C in the elution profile via iCCD analysis method, wherein the area of ​​the second polyethylene fraction is the area in the elution profile from 85°C to 120°C, and the area of ​​the second polyethylene fraction constitutes at least 20% of the total area of ​​the elution profile; (c) a third polyethylene fraction in the elution profile via iCCD analysis method within a temperature range of 70°C to 85°C, wherein the area of ​​the third polyethylene fraction is the area in the elution profile from 70°C to 85°C, and the area of ​​the third polyethylene fraction constitutes less than 10% of the total area of ​​the elution profile; The polyethylene composition has a viscosity of 0.880 g / cm 3 ~0.910g / cm 3 Density of 0.50 g / 10 min to 6.0 g / 10 min, melt index (I 2 ), and the polyethylene composition has a zero shear viscosity ratio of at least 1.0 and less than 2.0; The polyethylene composition is a polymer composition of ethylene and a C6 to C9 alkene. Polyethylene composition.

2. 2. The polyethylene composition of claim 1, further comprising a fourth polyethylene fraction comprising at least one peak in a temperature range of 20° C. to 35° C. in an elution profile via improved comonomer composition distribution (iCCD) analysis method, wherein the area of ​​the fourth polyethylene fraction is the area in said elution profile from 20° C. to 35° C., and wherein the area of ​​said fourth polyethylene fraction constitutes 0% to 35% of the total area of ​​said elution profile.

3. 3. The polyethylene composition according to claim 1 or 2, wherein the area of ​​the first polyethylene fraction constitutes 30% to 55% of the total area of ​​the elution profile.

4. 4. The polyethylene composition according to any one of claims 1 to 3, wherein the area of ​​the second polyethylene fraction constitutes between 20% and 45% of the total area of ​​the elution profile.

5. 5. The polyethylene composition according to any one of claims 1 to 4, wherein the area of ​​the third polyethylene fraction constitutes equal to or greater than 4% and less than 10% of the total area of ​​the elution profile.

6. 2. The polyethylene composition according to claim 1, wherein the polyethylene composition has a molecular weight distribution, expressed as the ratio of weight average molecular weight to number average molecular weight (Mw / Mn), in the range of 2.0 to 6.

0.

7. 2. The polyethylene composition according to claim 1, wherein the ratio of the molecular weight of the first polyethylene fraction to the molecular weight of the total area of ​​the elution profile is from 0.5 to 1.

5.

8. 2. The polyethylene composition of claim 1, wherein the polyethylene composition has a tan delta, measured at 0.1 rad / sec and 190° C., of 10 to 100.

9. A multilayer film, at least one layer comprising a polyethylene composition, said polyethylene composition comprising: (a) a first polyethylene fraction comprising at least one peak in a temperature range of 35° C. to 70° C. in an elution profile via an improved comonomer composition distribution (iCCD) analysis method, wherein the area of ​​the first polyethylene fraction is an area in the elution profile from 35° C. to 70° C., and the area of ​​the first polyethylene fraction constitutes 25% to 65% of the total area of ​​the elution profile; (b) a second polyethylene fraction comprising at least one peak in the temperature range of 85°C to 120°C in the elution profile via iCCD analysis method, wherein the area of ​​the second polyethylene fraction is the area in the elution profile from 85°C to 120°C, and the area of ​​the second polyethylene fraction constitutes at least 20% of the total area of ​​the elution profile; (c) a third polyethylene fraction in the elution profile via iCCD analysis method within a temperature range of 70°C to 85°C, wherein the area of ​​the third polyethylene fraction is an area in the elution profile from 70°C to 85°C, and the area of ​​the third polyethylene fraction constitutes less than 10% of the total area of ​​the elution profile; The polyethylene composition has a viscosity of 0.880 g / cm 3 ~0.910g / cm 3 Density of 0.50 g / 10 min to 6.0 g / 10 min, melt index (I 2 ), and the polyethylene composition has a zero shear viscosity ratio of at least 1.0 and less than 2.0; The polyethylene composition is a polymer composition of ethylene and a C6 to C9 alkene. Multilayer film.

10. 10. The multilayer film of claim 9, wherein the at least one layer comprising a polyethylene composition is a sealant layer.

11. The multilayer film of claim 10 further comprising a substrate layer.

12. 1. A method of producing an article, comprising:

13. A method comprising the steps of applying the polyethylene composition of claim 1 to at least one surface of a substrate layer, thereby forming an article comprising a sealant layer associated with said at least one surface of said substrate layer.

Citation Information

Patent Citations

  • Polyolefin composition

    JP2016505694A

  • Ethylene polymer composition for a film having improved toughness

    JP2017519080A

  • Resins for use as tie layers in multilayer films and multilayer films containing them

    JP2019530772A

  • olefin polymer

    JP2021505751A

  • Polymer Films Having Improved Heat Sealing Properties

    US20140256899A1